Method for producing polymer using poly (aryl ether sulfone) as reactant
Patent Information
- Application Number
- CN202380046682.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-09
- Filing Date
- 2023-06-14
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art is difficult to effectively recycle sulfone polymers, limiting their end use, and the polyarylethersulfone waste after industrial production is difficult to recycle, resulting in waste of resources and environmental pollution.
Use a pot to disrupt the polymer's repeated unit, and put it into the hypocritical and newly formed polymer chain in the reaction medium. Efficient re -cycle.
实现了砜聚合物的高效再循环,减少了资源浪费和环境污染,提高了生产效率和经济性,且所得聚合物在化学结构和特性方面与原生聚合物相似。
Smart Images

Figure BDA0005184544930000091 
Figure BDA0005184544930000101 
Figure BDA0005184544930000111
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to Indian Patent Application No. 202221034350 filed on June 15, 2022 and European Patent Application No. 22194749.2 filed on September 9, 2022, the entire contents of which are incorporated herein by reference for all purposes. Technical Field
[0003] The present disclosure relates to a chemical recycling process for making sulfone polymers using a recycled source of one or more poly(arylethersulfones) as reactants. Background Art
[0004] Products made of or incorporating plastic are part of almost any workplace or home environment. Typically, the plastic used to create these products is formed from virgin plastic material. That is, the plastic is produced from petroleum and is not made from existing plastic materials. Once these products have outlived their useful life, they are typically sent to waste disposal or recycling plants.
[0005] The ubiquity of plastics and the importance of environmental policies have led to an increasing importance of recycled plastic materials. Virgin polymer composition substitution is considered to represent an important way to solve the global plastic waste problem, prevent the depletion of limited natural resources and promote a circular economy. Recycling is one of the most important actions aimed at reducing petroleum use, CO2 emissions, hazards associated with waste disposal and high plastic pollution rates.
[0006] Recycled plastics have various benefits over virgin plastics produced from petroleum. Generally, the energy required to manufacture articles from recycled plastic materials derived from post-consumer and post-industrial waste materials and plastic waste (collectively referred to in this specification as "waste plastic materials") is less than the energy required to manufacture articles from like virgin plastics. Recycling plastic materials eliminates the need to dispose of plastic materials or products.
[0007] Generally, there are two ways to recycle plastics: physical recycling and chemical recycling. Mechanical recycling (also known as secondary recycling without changing the basic structure of the material) is a method of recovering waste plastic materials via mechanical means for reuse in the manufacture of plastic products. Compared to chemical recycling, clean and single types of plastics are more ideal for mechanical recycling when available in large quantities and are a win-win situation from an environmental and economic perspective. However, the availability of clean and homopolymer-based materials for mechanical recyclability is low. Chemical (tertiary) recycling is a term used to refer to advanced technological processes that convert plastic materials into smaller molecules (usually liquids or gases) that are suitable for use as raw materials for the production of new petrochemicals and plastics. Therefore, most previous methods for chemical recycling of polymer compositions include reusing polymers by depolymerization into lower molecular weight products that can only be used in applications other than the original target application.
[0008] In view of the demand for improved sustainability and circular economy, it is highly desirable to recycle polymers into the same intended applications. Such recycling will be regarded as an efficient resource utilization, wherein no waste is generated and the polymer is recycled back into the same application in which it was originally generated as waste (after its initial use). Such recycling methods will be eco-friendly and efficient. This will be an improvement over the prior art, in which polymers are recycled for less demanding applications, thus limiting their end uses. The reuse of polymers in their originally intended applications is generally quite limited.
[0009] Amorphous sulfone polymers are successfully used in modern industries such as automobiles, electronic devices, medical devices and aerospace, because sulfone polymers exhibit a unique property profile that includes not only the benefits of high strength and temperature resistance, but also inherent transparency and other properties. Therefore, they are particularly well suited for all applications where traditional materials such as glass and metal are to be replaced.
[0010] Examples of sulfone polymers prepared using recycled polymer waste can be found in US 2016 / 002431A1 (International Business Machines Corporation (IBM)), Hong et al. (Green Chemistry, 2017, Vol. 19, pp. 3692-3706), and Jones et al. (PNAS, July 12, 2016, Vol. 113 (28), pp. 7722-7726). These references describe the use of polycarbonate as a source of bisphenol A to prepare sulfone polymers with difluorodiphenyl sulfone and carbonate; the resulting polymer is a polysulfone polymer that is structurally different from the base polycarbonate material PC used as the source of bisphenol A monomer.
[0011] A method for preparing highly branched polyarylether polymers from linear polyarylether polymers is disclosed in US2005154178 A1 (Xerox). This method comprises (A) providing a reaction medium comprising: (i) an optional solvent, (ii) a polyfunctional phenolic compound having the formula Ar(OH)x, wherein x≥3 and wherein Ar is an aryl moiety or an alkylaryl moiety, provided that when Ar is an alkylaryl moiety, at least three of the -OH groups are bonded to its aryl moiety, (iii) one or more linear polyarylether polymers. In Examples I-III, linear polysulfone (PSU) is depolymerized and repolymerized with triol and cesium carbonate to produce highly branched polysulfone polymers having a significantly reduced molecular weight (Mw reduced by 2.7 to 4.2 times) compared to the initial linear polysulfone, and a significantly increased polydispersity index (PDI), which provides evidence of a much higher degree of branching of the polymer backbone. The resulting sulfone polymer is structurally different from its original linear polysulfone polymer. Furthermore, this reference is silent on recycling of polymer waste. Summary of the invention
[0012] The present invention is as disclosed hereinafter and in the appended claims.
[0013] The present invention addresses the recyclability of sulfone polymers, wherein the polymers are efficiently recycled by a one-pot process that disrupts the polymer repeating units and incorporates them into newly formed polymer chains from oligomers and monomers in the reaction medium. Since monomers can be added to the reaction medium, the type of sulfone polymer obtained after the process can be identical in chemical structure and in properties when the added monomers correspond to the same monomers from which the recycled sulfone polymers are derived. On the other hand, when the monomers added to the reaction medium produce different types of sulfone repeating units, then the resulting polymer contains not only repeating units derived from the recycled sulfone polymer, but also other repeating units from the added monomers.
[0014] Another benefit is the recycling of virgin polyarylethersulfone produced in commercial plant operations or post-industrial polyarylethersulfone waste that does not meet certain product specifications, sometimes referred to as "off-spec" polyarylethersulfone (e.g., high yellow index, polymer produces turbid solutions, Mw is too low or too high for a particular intended application, such as unsuitable for forming films or fibers for membrane applications). This polyarylethersulfone waste that does not meet certain product specifications becomes unmarketable and therefore is often disposed of in landfills. By using this method, polyarylethersulfone manufacturing commercial plants can achieve near 100% efficiency and reduce their environmental footprint while improving production economics.
[0015] A first aspect of the present invention provides a method for producing polyarylethersulfone (P2) using a recycled polymer material containing polyarylethersulfone (P1) as a reactant, the method comprising
[0016] Adding a polar aprotic solvent (S) to the reactor vessel;
[0017] adding recycled polymer material containing polyarylethersulfone (P1) to the reactor vessel;
[0018] Adding a basic salt-forming agent (A) to the reactor vessel;
[0019] adding at least one monomer (M) selected from the group consisting of at least one aromatic diol monomer (AA) and at least one aromatic dihalogenated monomer (BB) to the reactor vessel;
[0020] whereby said adding step forms a reaction medium (RM) comprising: the recycled polymer material containing the polyarylethersulfone (P1), at least one monomer (M), the basic salt-forming agent (A) and the polar aprotic solvent (S),
[0021] heating the reaction medium to reach a reaction temperature of at least 150° C. to form polyarylethersulfone (P2); and
[0022] separating the polyarylethersulfone (P2) formed from the reaction medium;
[0023] The alkaline salt-forming agent (A) is an alkali metal carbonate and / or an alkali metal hydroxide.
[0024] The aromatic diol monomer (AA) may be selected from the group consisting of 4,4'-biphenol, bisphenol A, bisphenol S, isosorbide, isomannide, isoidol, tetramethylbisphenol F, hydroquinone, and any combination thereof, preferably selected from the group consisting of 4,4'-biphenol, bisphenol A, bisphenol S, tetramethylbisphenol F, hydroquinone, and any combination thereof.
[0025] The aromatic dihalogenated monomer (BB) may be selected from the group consisting of 4,4'-difluorodiphenyl sulfone (DFDPS), 4,4'-dichlorodiphenyl sulfone (DCDPS), disulfonated DCDPS, disulfonated DFDPS, and any combination thereof, preferably selected from the group consisting of DCDPS, disulfonated DCDPS, and combinations thereof.
[0026] The polyarylethersulfone (P1) is derived from at least one aromatic diol monomer (AA') and at least one aromatic dihalogenated monomer (BB') by condensation, wherein:
[0027] - the added aromatic diol monomer (AA) may be the same as or different from the aromatic diol monomer (AA');
[0028] The added aromatic dihalogenated monomer (BB) may be the same as or different from the aromatic dihalogenated monomer (BB').
[0029] A second aspect of the present invention relates to a PAES (P2) obtained by the process according to the present invention.
[0030] A third aspect of the present invention provides the use of PAES (P2) for preparing an article (or a part thereof).
[0031] Another aspect of the present invention provides a product comprising a PAES (P2) according to the present invention. DETAILED DESCRIPTION
[0032] In this application:
[0033] - even if any description relating to a specific embodiment is applicable to and interchangeable with other embodiments of the present disclosure, and each embodiment defined thereby can be combined with another embodiment, unless otherwise indicated or clearly incompatible;
[0034] - When an element or component is said to be included in and / or selected from a list of listed elements or components, it should be understood that in the relevant embodiments explicitly considered herein, the element or component may also be any of these listed independent elements or components, or may also be selected from a group consisting of any two or more of the explicitly listed elements or components; any element or component listed in the list of elements or components may be omitted from this list;
[0035] - Any recitation of numerical ranges by endpoints herein includes all numbers contained in the recited range as well as the endpoints of that range and equivalents thereof;
[0036] - the terms “comprising” or “comprise” include “consisting essentially of” or “consisting essentially of” as well as “consisting of” or “consisting of”; and
[0037] - as used herein, the singular 'a' or 'one' includes the plural unless expressly stated otherwise; and
[0038] -It should be understood that the elements, properties and / or characteristics of the (co)polymers, products or articles, methods or uses described in this specification can be combined in all possible ways with other elements, properties and / or characteristics of the (co)polymers, products or articles, methods or uses, explicitly or implicitly, without departing from the scope of this specification.
[0039] The term "consisting essentially of" in connection with a composition, product, polymer, solution, process, method, etc., is intended to mean that any additional elements or features that may not be expressly described herein and that do not materially affect the basic and novel features of such composition, product, polymer, solution, process, method, etc. may be included in such an embodiment. For example, when a composition, compound, product, polymer, or solution "consists essentially of the required elements," it is generally understood that any additional element may be present in an amount not exceeding 1 wt % based on the total weight of the composition, compound, product, polymer, solution, etc. or not exceeding 1 mol % based on the total moles of the composition, compound, product, polymer, or solution.
[0040] In the present disclosure, the term "repeating unit" refers to the smallest unit of the PAES polymer, which is repeated in the chain and is composed of the condensation of the diol compound and the dihalogenated compound. The term "recurring unit" is synonymous with the terms "repeating unit" and "structural unit".
[0041] As used herein, the term "homopolymer" encompasses polymers having only one type of repeating unit.
[0042] As used herein, the term "copolymer" encompasses polymers that may have two or more different types of repeating units.
[0043] The term "solvent" is used herein in its ordinary sense and refers to a substance that is capable of dissolving another substance (solute) to form a mixture that is uniformly dispersed at the molecular level. In the case of polymer solutes, the convention is to refer to a solution of the polymer in the solvent when the resulting mixture is transparent and there is no visible phase separation in the system. The point at which phase separation occurs, often referred to as the "cloud point," is considered to be the point at which the solution becomes cloudy or turbid due to the formation of polymer aggregates.
[0044] The term "membrane" is used herein in its ordinary sense, i.e., it refers to a discrete, generally thin interface that attenuates the permeation of chemicals in contact with it. Membranes typically comprise polymers. Examples of membranes are water purification membranes and hemodialysis membranes.
[0045] The term "post-consumer" polymeric material (or article) refers to a finished product that has been used and then recycled; this can provide a source of recycled polymeric material that can be used in the present method. Typical post-consumer polymeric materials can include, but are not limited to, packaging, films, compounds, automotive parts, electronic parts, consumer product parts (such as but not limited to plastic bottles and especially milk bottles), battery parts, or any used or end-of-life three-dimensional injection molded, extruded or printed articles or parts thereof.
[0046] The term "post-industrial" polymeric material (or article) (also referred to as "pre-consumer" polymeric material (or article)) refers to waste generated by manufacturing processes that result in the production of source polymeric materials that can be used in the present method. For example, when a polymer is formed into a bottle, polymer waste may be generated and they do not ultimately appear in the final bottle product. If these polymer wastes are ground, shredded or re-granulated and used again to make the same article or another article, they will be referred to as "post-industrial" polymeric materials. Typical pre-consumer polymeric materials may include, but are not limited to, whole packaging articles, parts thereof, or waste thereof, films, fibers, membranes, off-specification compounds or polymer products including off-specification polyarylethersulfones, automotive parts, electronic parts, consumer product parts (such as plastic bottles and particularly milk bottles), battery parts, or any three-dimensional injection molded, extruded or printed articles or parts thereof.
[0047] In other words, post-consumer polymer material (or article or waste) refers to finished products, whereas post-industrial polymer material (or article or waste) refers to waste material generated by a manufacturing process for making polymers or polymer-based articles.
[0048] Weight average molecular weight (M w ) and number average molecular weight (M n ) can be estimated by gel permeation chromatography (GPC) calibrated with polystyrene standards. The mobile phase can be selected from any solvent for the polymers described herein, for example, one or more solvents described herein, such as dichloromethane, N-alkyl-2-pyrrolidone (such as N-methyl-2-pyrrolidone (NMP), N-butyl-2-pyrrolidone, etc.), dimethyl sulfoxide (DMSO), 1,3-dimethyl-2-imidazolidinone (DMI), tetramethylene sulfone (sulfolane), N,N′-dimethylacetamide (DMAc), or any mixture thereof. The polydispersity index (PDI) is hereby expressed as the weight average molecular weight (M w ) and number average molecular weight (M n ) ratio.
[0049] Should the disclosure of any patents, patent applications, and publications incorporated herein by reference conflict with the description of the present application to the extent that it renders a term unclear, the present description shall take precedence.
[0050] One aspect of the present invention relates to a method for chemically recycling a polymer material comprising polyarylethersulfone (P1) [hereinafter "PAES(P1)"], the method comprising
[0051] Adding a polar aprotic solvent (S) to the reactor vessel;
[0052] Adding the polymer material containing PAES (P1) to the reactor vessel;
[0053] Adding a basic salt-forming agent (A) to the reactor vessel;
[0054] adding at least one monomer (M) selected from the group consisting of at least one aromatic diol monomer (AA) and at least one aromatic dihalogenated monomer (BB) to the reactor vessel;
[0055] whereby said adding step forms a reaction medium (RM) comprising: the polymer material containing the PAES (P1), the at least one monomer (M), the basic salt-forming agent (A) and the polar aprotic solvent (S),
[0056] heating the reaction medium to reach a reaction temperature of at least 150° C. to form polyarylethersulfone (P2) [hereinafter “PAES(P2)”]; and
[0057] separating the formed PAES (P2) from the reaction medium;
[0058] in
[0059] - this PAES (P1) is derived by condensation from at least one aromatic diol monomer (AA') and at least one aromatic dihalogenated monomer (BB'),
[0060] - the aromatic diol monomer (AA) and the aromatic diol monomer (AA') are the same or different;
[0061] - the aromatic dihalogenated monomers (BB) are the same as or different from the aromatic dihalogenated monomer (BB'); and
[0062] - The basic salt-forming agent (A) is an alkali metal carbonate and / or an alkali metal hydroxide.
[0063] The aromatic diol monomer (AA) may be selected from the group consisting of 4,4'-biphenol, bisphenol A, bisphenol S, isosorbide, isomannide, isoidol, tetramethylbisphenol F, hydroquinone, and any combination thereof, preferably selected from the group consisting of 4,4'-biphenol, bisphenol A, bisphenol S, tetramethylbisphenol F, hydroquinone, and any combination thereof.
[0064] The aromatic dihalogenated monomer (BB) may be selected from the group consisting of 4,4'-difluorodiphenyl sulfone (DFDPS), 4,4'-dichlorodiphenyl sulfone (DCDPS), disulfonated DCDPS, disulfonated DFDPS, and any combination thereof, preferably selected from the group consisting of DCDPS, disulfonated DCDPS, and combinations thereof.
[0065] In a preferred embodiment, the polymer material comprises at least one recycled material selected from the group consisting of: post-consumer polymer articles, post-industrial polymer articles including article waste, off-specification polyarylethersulfone products; and any combination thereof. These articles are preferably selected from the group consisting of: films, automotive parts, electronic parts, consumer product parts such as milk bottles, composite materials, battery parts, and any combination thereof.
[0066] Polyarylethersulfone (P1)
[0067] The recycled polymer material used as reactant in the process of the invention comprises at least one polyarylethersulfone (P1).
[0068] PAES (P1) may be a polymer comprising at least 50 mol.%, at least 60 mol.%, at least 70 mol.%, at least 80 mol.%, at least 90 mol.%, at least 95 mol.%, or at least 98 mol.% of at least one repeating unit selected from those having the following formulae, based on the total moles of repeating units of PAES (P1): (L), (L'), (M), (M'), (N), (N'), (O), (O'), (T), (T'), (U), (U'), (V), (V'), (W), (W'):
[0069]
[0070]
[0071]
[0072]
[0073] in:
[0074] - each R is independently selected from the group consisting of halogen, alkyl, alkenyl, alkynyl, aryl, ether, thioether, carboxylic acid, ester, amide, imide, alkali metal or alkaline earth metal sulfonate, alkyl sulfonate, alkali metal or alkaline earth metal phosphonate, alkyl phosphonate, amine and quaternary ammonium; and
[0075] - Each i is independently an integer from 1 to 4.
[0076] The repeating unit selected from those having formula (U), (V), (W) may be represented by the formula (U*), (V*), (W*), respectively:
[0077]
[0078]
[0079] PAES (P1) may be a homopolymer having one repeating unit selected from those having formula (L), (L'), (N), (N'), (O), (O'), (Q), (Q'), (T), (T'), (U), (U'), (V), (V'), (W), (W'), (U*), (V*), (W*), or may be a copolymer comprising two or more repeating units selected from those having formula (L), (L'), (N), (N'), (O), (O'), (Q), (Q'), (T), (T'), (U), (U'), (V), (V'), (W), (W'), (U*), (V*), (W*). In some embodiments, each R in a repeating unit selected from those having formula (L'), (N'), (O'), (Q'), (T'), (U'), (V'), and (W') as provided above can be independently selected from the group consisting of alkali or alkaline earth metal sulfonates and alkyl sulfonates, and each i is independently selected from an integer from 1 to 4.
[0080] In particular, the PAES (P1) may be a copolymer comprising or consisting essentially of at least 60 mol.% of the following, based on the total moles of repeating units in PAES (P1):
[0081] - repeating units of formula (L) and (L'),
[0082] - repeating units of formula (N) and (N'),
[0083] - repeating units of formula (O) and (O'),
[0084] - repeating units of formula (Q) and (Q'),
[0085] - repeating units of formula (T) and (T'),
[0086] - repeating units of formula (U) and (U'),
[0087] - repeating units of formula (V) and (V'), or
[0088] - repeating units of formula (W) and (W'),
[0089] wherein each R in the repeating units of formula (L'), (N'), (O'), (Q'), (T'), (U'), (V') and (W') can be independently selected from the group consisting of alkali metal or alkaline earth metal sulfonates and alkyl sulfonates, and each i is independently selected from an integer from 1 to 4.
[0090] In a preferred embodiment, in the method for producing polyarylethersulfone (P2) using a recycled polymer material comprising polyarylethersulfone (P1) as a reactant, the PAES (P1) preferably comprises at least 50 wt.%, at least 60 wt.%, at least 70 wt.%, at least 80 wt.%, at least 90 wt.%, or at least 95 wt.% of a sulfone polymer selected from the group consisting of:
[0091] -PPSU,
[0092] -PSU,
[0093] -PES,
[0094] - Sulfonated PSU (sPSU),
[0095] - Sulfonated PES (sPES),
[0096] -sulfonated PPSU (sPPSU),
[0097] - any polymer derived from a diol monomer selected from isosorbide and / or tetramethylbisphenol F and a dihalogenated monomer selected from sulfonated dihalodiphenyl sulfone and / or dihalodiphenyl sulfone,
[0098] - any copolymer derived from at least two diols selected from diphenol, bisphenol A, bisphenol S, isosorbide, tetramethylbisphenol F and / or hydroquinone and a dihalogenated monomer selected from sulfonated dihalodiphenyl sulfones and / or dihalodiphenyl sulfones,
[0099] - a block polymer of AB or ABA form comprising at least one block having one repeating unit selected from those of formula (L), (L'), (N), (N'), (O), (O'), (Q), (Q'), and at least one block having one repeating unit selected from those of formula (T), (T'), (U), (U'), (V), (V'), (W), (W'), (U*), (V*), (W*);
[0100] - a block copolymer of AB or ABA form comprising at least one block having one repeating unit selected from those having formula (L), (L'), (N), (N'), (O), (O'), (Q), (Q'), and at least one polyalkylene oxide or polyvinylpyrrolidone (PVP) block, such as a PEG block, a PPG block or a PVP block; and
[0101] - any combination of two or more thereof,
[0102] wherein the formulae (L), (L'), (N), (N'), (O), (O'), (Q), (Q'), (T), (T'), (U), (U'), (V), (V'), (W), (W'), (U*), (V*), and (W*) are as previously defined.
[0103] As used herein, polyethersulfone (PES) comprises at least 90 mol.%, at least 95 mol.%, or at least 98 mol.% of repeating units (R) having formula (O) PES ) or consists essentially of it, mol.% is based on the total moles of repeating units in the PES polymer. PES can be prepared by known methods and is particularly available from Solvay Specialty Polymers USA, LLC. PES available.
[0104] As used herein, polysulfone (PSU) comprises at least 90 mol.%, at least 95 mol.%, or at least 98 mol.% of repeating units (R) having formula (L) PSU ) or consists essentially of it, mol.% is based on the total moles of repeating units in the PSU polymer. PSU can be prepared by known methods and is available in particular from Solvay Specialty Polymers, Inc., USA. PSU available.
[0105] As used herein, polyphenylsulfone (PPSU) comprises at least 90 mol.%, at least 95 mol.%, or at least 98 mol.% of repeating units (R) having formula (Q) PPSU ) or consists essentially of it, mol.% is based on the total moles of repeating units in the PPSU polymer. PPSU can be prepared by known methods and is available in particular from Solvay Specialty Polymers, Inc., USA. PPSU available.
[0106] As used herein, sulfonated polyethersulfone (sPES) comprises at least 60 mol.%, at least 70 mol.%, at least 80 mol.%, at least 90 mol.%, at least 95 mol.%, or at least 98 mol.% of repeating units (R) having formula (O) PES ) and a repeating unit (R) having the formula (O') sPES ) or consists essentially of a combination of, mol. % is based on the total moles of repeating units in the sPES polymer, wherein each R in the formula (O') is independently selected from the group consisting of alkali metal or alkaline earth metal sulfonates and alkyl sulfonates; and each i is independently an integer from 1 to 4.
[0107] As used herein, sulfonated polysulfone (sPSU) comprises at least 60 mol.%, at least 70 mol.%, at least 80 mol.%, at least 90 mol.%, at least 95 mol.%, or at least 98 mol.% of repeating units (R) having formula (L) PSU ) and a repeating unit (R) having the formula (L') sPSU ) or consists essentially of it, mol. % is based on the total moles of repeating units in the sPSU polymer, wherein each R in the formula (L') is independently selected from the group consisting of alkali metal or alkaline earth metal sulfonates and alkyl sulfonates; and each i is independently an integer from 1 to 4.
[0108] As used herein, sulfonated polyphenylene sulfone (sPPSU) comprises at least 60 mol.%, at least 70 mol.%, at least 80 mol.%, at least 90 mol.%, at least 95 mol.%, or at least 98 mol.% of repeating units (R) having formula (Q) PPSU ) and a repeating unit (R) having the formula (Q') sPPSU ) or consists essentially of it, mol. % is based on the total moles of repeating units in the sPPSU polymer, wherein each R in the formula (Q') is independently selected from the group consisting of alkali metal or alkaline earth metal sulfonates and alkyl sulfonates; and each i is independently an integer from 1 to 4.
[0109] When used, the block polymer in the AB or ABA form in PAES (P1) may comprise
[0110] at least one sulfone polymer block having at least one repeating unit selected from those of PPSU, sPPSU, PSU, sPSU, PES, sPES, and at least one block having repeating units made from tetramethylbisphenol F and sulfonated or non-sulfonated dihalodiphenyl sulfone or from 1,4:3,6-dianhydrohexitol sugar diol (e.g., isosorbide) and sulfonated or non-sulfonated dihalodiphenyl sulfone; or
[0111] - at least one block polymer having repeating units selected from those of PPSU, sPPSU, PSU, sPSU, PES, sPES, and at least one polyalkylene oxide or polyvinylpyrrolidone (PVP) block, such as a PEG block, a PPG block or a PVP block.
[0112] As used herein, a polyvinylpyrrolidone (PVP) block or polymer may comprise or may consist essentially of at least 90 mol.%, at least 95 mol.%, or at least 98 mol.%, of a repeating unit Rp having the formula:
[0113]
[0114] wherein n is an integer of at least 3, or at least 5, or at least 8, or at least 10, or at least 20, or at least 30, or at least 40, or at least 50, and at most 200, or at most 175, or at most 150, or at most 100.
[0115] As used herein, "polyalkylene oxide" is understood to mean those obtained by polymerization of alkylene oxides such as ethylene oxide, 1,2-propylene oxide. "Polyalkylene oxide" can generally be represented by the following formula: - [(CHR l ) y O] z —H, where R l is H or an alkyl group; y may be 1 to 3; and z may be 2 to 500. Polyethylene glycol (PEG) and polypropylene glycol (PPG) are examples of polyalkylene oxides.
[0116] In a further more preferred embodiment, in a method for producing polyarylethersulfone (P2) using a recycled polymer material comprising polyarylethersulfone (P1) as a reactant, the PAES (P1) comprises or consists of at least 50 wt.%, at least 60 wt.%, at least 70 wt.%, at least 80 wt.%, at least 90 wt.% or at least 95 wt.% of a sulfone polymer selected from the group consisting of PPSU, PSU, PES, sPSU, sPES, sPPSU, and any combination thereof, the wt.% being based on the total weight of the PAES (P1).
[0117] In an alternative embodiment, in a method for producing polyarylethersulfone (P2) using a recycled polymer material containing polyarylethersulfone (P1) as a reactant, the PAES (P1) may in some cases be composed of a blend of PES / PPSU, PES / PSU, PSU / PPSU, PES / PSU / PPSU, PES / sPES, PSU / sPSU, or PPSU / sPPSU.
[0118] The PAES (P1) polymer can be produced by various methods. The PAES (P1) is preferably derived from at least one aromatic diol monomer (AA') and at least one aromatic dihalogenated monomer (BB') by polycondensation.
[0119] For example, U.S. Pat. Nos. 4,108,837 and 4,175,175 describe the preparation of polyarylethers and in particular polyarylethersulfones. Several one-step and two-step methods are described in these patents, which are incorporated herein by reference in their entirety. In these methods, a double alkali metal salt of a dihydric phenol (aromatic diol AA') is reacted with a dihalogenated benzene compound (aromatic dihalogenated BB') in the presence of a polar aprotic solvent under substantially anhydrous conditions. In the two-step method, the aromatic diol AA' is first converted in situ into an alkali metal salt derivative by reaction with an alkali metal or alkali metal compound in the presence of a solvent. Alkali metal salts are produced as by-products of the polymerization.
[0120] For PAES (P1) production, the preferred starting aromatic diol monomer (AA') can be selected from the group consisting of: 4,4'-biphenol, bisphenol A, bisphenol S (4,4'-dihydroxydiphenyl sulfone), 1,4:3,6-dianhydrohexitol sugar diol (such as isosorbide), tetramethylbisphenol F, hydroquinone, and any combination thereof.
[0121] For the production of PAES (P1), the preferred starting aromatic dihalogenated monomer (BB') can be selected from the group consisting of: 4,4'-dihalodiphenyl sulfone and its sulfonated derivatives, preferably selected from 4,4'-difluorodiphenyl sulfone (DFDPS), 4,4'-dichlorodiphenyl sulfone (DCDPS), disulfonated DCDPS, and / or disulfonated DFDPS, and any combination thereof, more preferably selected from DCDPS and / or disulfonated DCDPS.
[0122] In some embodiments for making PAES (P1) copolymers, the first aromatic diol monomer (AA') 1 can be selected from the group consisting of: 4,4'-biphenol, bisphenol A, bisphenol S and hydroquinone, and the second aromatic diol monomer (AA') 2 can be selected from the group consisting of: tetramethyl bisphenol F, 1,4:3,6-dianhydrohexitol sugar diol (such as isosorbide), and any combination thereof.
[0123] The weight average molecular weight Mw of PAES (P1) can be 30,000 g / mol to 100,000 g / mol, for example 35,000 g / mol to 90,000 g / mol or 40,000 g / mol to 85,000 g / mol. The weight average molecular weight (Mw) of PAES (P1) can be determined by gel permeation chromatography (GPC) using dichloromethane as mobile phase (2×5μ mixed D column with guard column from Agilent Technologies; flow rate: 1.5 mL / min; injection volume: 20 μL of 0.2 w / v% sample solution), calibrated with polystyrene standards.
[0124] Polyarylethersulfone (P2)
[0125] The process of the present invention forms polyarylethersulfone (P2).
[0126] PAES(P2) may be a polymer comprising at least 50 mol % of at least one repeating unit selected from the group consisting of repeating units having the following formulae as previously provided for PAES(P1): (L), (L'), (N), (N'), (O), (O'), (Q), (Q'), (T), (T'), (U), (U'), (V), (V'), (W), (W'), (U*), (V*), (W*), based on the total moles of repeating units in PAES(P1). PAES (P2) may be a homopolymer having repeating units selected from those having formula (L), (L'), (N), (N'), (O), (O'), (Q), (Q'), (T), (T'), (U), (U'), (V), (V'), (W), (W'), (U*), (V*), (W*), or may be a copolymer comprising two or more repeating units selected from those having formula (L), (L'), (N), (N'), (O), (O'), (Q), (Q'), (T), (T'), (U), (U'), (V), (V'), (W), (W'), (U*), (V*), (W*). In a preferred embodiment, each R in a repeating unit selected from those having formula (L'), (N'), (O'), (Q'), (T'), (U'), (V') and (W') can be independently selected from the group consisting of alkali metal or alkaline earth metal sulfonates and alkyl sulfonates, and each i is independently selected from an integer from 1 to 4.
[0127] In particular, the PAES (P2) may be a copolymer comprising or consisting essentially of at least 60 mol.% of the following, based on the total moles of repeating units in PAES (P2):
[0128] - a repeating unit having the formula (L), (L'),
[0129] - a repeating unit having the formula (N), (N'),
[0130] - a repeating unit having the formula (O), (O'),
[0131] - a repeating unit having the formula (Q), (Q'),
[0132] - a repeating unit having the formula (T), (T'),
[0133] - a repeating unit having the formula (U), (U'),
[0134] - a repeating unit having the formula (V), (V'), or
[0135] - a repeating unit having the formula (W), (W'),
[0136] wherein each R in the repeating units of formula (L'), (M'), (N'), (O'), (T'), (U'), (V') and (W') can be independently selected from the group consisting of alkali metal or alkaline earth metal sulfonates and alkyl sulfonates, and each i is independently an integer from 1 to 4.
[0137] When PAES(P1) added as a reactant in (RM) comprises a repeating unit selected from those repeating units having the formula (L), (L'), (N), (N'), (O), (O'), (Q), (Q'), (T), (T'), (U), (U'), (V), (V'), (W), (W'), PAES(P2) also comprises the same repeating units as in PAES(P1). However, the mol.% content of such repeating units in PAES(P2) based on the total moles of the repeating units in PAES(P2) may be different from the mol.% content of such repeating units in PAES(P1). For example, when PAES (P1) is a PPSU consisting essentially of repeating units of formula (Q) and the at least one monomer (M) added to the reaction consists of a combination of diphenol and sulfonated DCDPS, the resulting PAES (P2) contains not only repeating units of formula (Q') but also the same repeating units (Q), although their content in PAES (P2) will be less than 100 mol.%, based on the total moles of repeating units in PAES (P2).
[0138] The PAES (P2) preferably comprises at least 50 wt.%, at least 60 wt.%, at least 70 wt.%, at least 80 wt.%, at least 90 wt.%, or at least 95 wt.% of a sulfone polymer selected from the group consisting of:
[0139] -PPSU;
[0140] -PSU;
[0141] -PES;
[0142] - Sulfonated PSU (sPSU);
[0143] - Sulfonated PES (sPES);
[0144] -Sulfonated PPSU (sPPSU);
[0145] - a copolymer derived from a diol selected from 4,4'-biphenol, bisphenol A, bisphenol S or hydroquinone, and two dihalogenated monomers selected from disulfonated DCDPS+DCDPS or DFDPS+disulfonated DFDPS;
[0146] a homopolymer derived from a diol selected from isosorbide or tetramethylbisphenol F, and a dihalogenated monomer selected from disulfonated DCDPS, DCDPS, DFDPS or disulfonated DFDPS; and
[0147] - a copolymer derived from two diols selected from 4,4′-biphenol, bisphenol A, bisphenol S, isosorbide, tetramethylbisphenol F and hydroquinone, and a dihalogenated monomer selected from disulfonated DCDPS and / or DCDPS.
[0148] More preferably, the PAES (P2) comprises at least 50 wt.% of a sulfone polymer selected from the group consisting of PPSU, PSU, PES, sPSU, sPES, sPPSU, and any combination thereof, the wt.% being based on the total weight of the PAES (P2).
[0149] PAES (P2) may have a Mw of at least 40 kDa, at least 50 kDa, or at least 55 kDa, and / or at most 150 kDa, at most 130 kDa, at most 110 kDa, at most 100 kDa, or at most 90 kDa. (P2) , the Mw (P2) It was measured via a GPC method using dichloromethane as the mobile phase and calibrated with polystyrene standards. (P2) A preferred range of may be 50 kDa to 100 kDa or 55 kDa to 90 kDa.
[0150] In some embodiments, PAES(P2) has a Mw of PAES(P1). (P1) Mw within + / -35% (P2) ; and / or PAES(P2) has a PDI of PAES(P1) P1 PDI within + / -35% of valueP2 value.
[0151] In particular, the weight average molecular weight (Mw) and number average molecular weight (M n ) can be determined by gel permeation chromatography (GPC) using dichloromethane as the mobile phase (2×5μ Mixed D column with guard column from Agilent Technologies; flow rate: 1.5 mL / min; injection volume: 20 μL of 0.2 w / v % sample solution), calibrated with polystyrene standards.
[0152] The polydispersity index (PDI) is hereby expressed as the weight average molecular weight (M w ) and number average molecular weight (M n ) ratio.
[0153] Recycled polymer materials
[0154] The recycled polymeric material to be added to the reaction medium (RM) in the process of the present invention may be considered waste, such as end-of-life products or articles, industrial waste and / or unmarketable (e.g., off-specification, surplus) products or articles.
[0155] The polymeric material preferably comprises at least one recycled material selected from the group consisting of: a post-consumer polymeric article, a post-industrial polymeric article or parts thereof, an off-specification polyarylethersulfone product; and any combination thereof.
[0156] The polymeric material may include or consist of at least one recycled polymeric article selected from the group consisting of films, automotive parts, electronic parts, consumer product parts such as plastic bottles (e.g., milk bottles), composite materials, battery parts, any parts or waste thereof, and any combination thereof.
[0157] The recycled polymer material may comprise at least 50% by weight (wt.%) PAES (P1) based on the total weight of the polymer material. The polymer material preferably comprises at least 55% wt.%, at least 60% wt.%, at least 65% wt.%, at least 70% wt.%, at least 75% wt.%, at least 80% wt.%, at least 85% wt.%, at least 90% wt.%, at least 95% wt.%, or at least 99% wt.% PAES (P1) based on the total weight of the polymer material.
[0158] The recycled polymer material may consist essentially of PAES(P1).
[0159] In alternative embodiments, the recycled polymer material comprises PAES (P1) and at least one additional component, such as other non-PAES polymers, fillers, and / or additives.
[0160] Other polymers (P3) that can be used in polymer materials
[0161] The recycled polymer material may further comprise another polymer (P3) different from PAES (P1). The other polymer (P3) is preferably not PAES, also referred to as "non-PAES polymer".
[0162] The other polymer (P3) in the recycled polymer material may preferably be a pore-forming polymer, such as polyvinylpyrrolidone (PVP), polyalkylene oxide, or polyalkylene glycol such as polyethylene glycol (PEG), or any combination thereof.
[0163] In some cases, when the recycled polymeric material further comprises another polymer (P3), the polymeric material may comprise:
[0164] - a blend of PAES (P1) and another polymer (P3),
[0165] - a coating or layer of one of the polymers (P1) and (P3) on top of at least a portion of a solid surface made of the other polymer, and / or
[0166] - a block copolymer comprising at least one block of PAES (P1) and at least one further block of another polymer (P3).
[0167] For example, the recycled polymer material may comprise a blend of PAES (P1) and a pore-forming polymer as polymer (P3), such as polyvinylpyrrolidone (PVP), a polyalkylene oxide or polyalkylene glycol (e.g., PEG, PPG) having a molecular weight of at least 200, preferably 200 to 900, or any combination thereof.
[0168] In another example, the recycled polymer material may comprise as polymer (P3) a block copolymer in the form of AB or ABA, wherein blocks A and B represent at least one PAES (P1) block and at least one polyalkylene oxide block, such as PES:PEG, PPSU:PEG or PSU:PEG block copolymers.
[0169] In other embodiments, the other polymer (P3) in the recycled polymer material may be polycarbonate (PC).
[0170] The recycled polymeric material preferably comprises at most 25 wt.%, at most 20 wt.%, at most 15 wt.%, at most 10 wt.%, or at most 5 wt.% of the other one or more polymers (P3), based on the total weight of the recycled polymeric material.
[0171] Optional solid fillers in polymer materials
[0172] The recycled polymer material may further comprise a solid filler. The filler is preferably non-polymeric. The filler may be a reinforcing filler. In fact, when it is desired to form a polymer molded article with reduced weight but high mechanical strength, the polymer material may be reinforced by a filler.
[0173] In such a case, the recycled polymeric material preferably contains at most 60 wt.%, at most 55 wt.%, at most 50 wt.%, at most 45 wt.%, at most 40 wt.%, at most 35 wt.%, or at most 30 wt.% of filler, and / or at least 2 wt.%, at least 4 wt.%, at least 6 wt.%, at least 8 wt.%, or at least 10 wt.% of filler, the wt.% being based on the total weight of the recycled polymeric material.
[0174] Filler can be in the form of particulate filler, non-fibrous filler and fibrous filler.Particulate reinforcing filler can be selected from mineral filler (such as talc, mica, kaolin, calcium carbonate, calcium silicate and magnesium carbonate) or glass ball (for example, hollow glass microsphere).Fibrous reinforcing filler is considered to be a three-dimensional material with length, width and thickness in this article, wherein the average length is significantly greater than both width and thickness.Usually, this fibrous material has at least 5, at least 10, at least 20 or at least 50 aspect ratios, and the aspect ratio is defined as the ratio between the maximum in average length and average width and average thickness.Fibrous reinforcing filler can be selected from glass fiber, carbon fiber, aramid fiber, aluminum fiber, titanium fiber, magnesium fiber, boron carbide fiber, rock wool fiber, and / or steel fiber.Aramid fiber will be considered to be a polymer filler." non-fibrous " filler is considered to have a three-dimensional structure (with length, width and thickness) in this article, wherein both length and width are significantly greater than its thickness.Non-fibrous reinforcing filler can contain glass or carbon.
[0175] In a preferred embodiment, the recycled polymer material may further comprise a non-polymer filler selected from mineral fillers, carbon fibers, and / or glass fibers.
[0176] One or more optional additives in the polymer material
[0177] The recycled polymer material may further comprise one or more additional additives selected from the group consisting of UV stabilizers, heat stabilizers, acid scavengers (i.e. zinc oxide, magnesium oxide), antioxidants, pigments, processing aids, lubricants, flame retardants, and / or conductive additives (i.e. carbon black, carbon nanotubes and carbon nanofibrils).
[0178] In such a case, the recycled polymer material preferably contains at most 15 wt.%, at most 10 wt.%, at most 7.5 wt.%, or at most 5 wt.% of one or more additional additives, and / or at least 0.01 wt.%, at least 0.05 wt.%, at least 0.08 wt.%, at least 0.1 wt.%, or at least 1 wt.% of one or more additional additives, the wt.% being based on the total weight of the recycled polymer material.
[0179] Monomer (M) in the reaction medium
[0180] Prior to the start of the polycondensation reaction, at least one monomer (M) selected from at least one aromatic diol monomer (AA) and / or at least one aromatic dihalogenated monomer (BB) is added to the reactor vessel.
[0181] Preferably, the at least one monomer (M) comprises at least one aromatic diol monomer (AA). The at least one monomer (M) preferably comprises at least 50 mol.%, at least 60 mol.%, at least 70 mol.%, at least 80 mol.%, at least 90 mol.%, at least 95 mol.%, or at least 99 mol.% of at least one aromatic diol monomer (AA), based on the total moles of monomer (M).
[0182] When the PAES (P1) recycling ratio is 100 wt.%, the at least one monomer (M) preferably consists essentially of at least one aromatic diol monomer (AA).
[0183] Among the diol monomers (AA) suitable for use in the process of the invention, mention may especially be made of the following compounds:
[0184]
[0185]
[0186] and / or the three isomers of 1,4:3,6-dianhydrohexitol sugar diol, namely isosorbide (1), isomannide (2) and isoidide (3):
[0187]
[0188] The aromatic diol monomer (AA) may be selected from the group consisting of isosorbide (1), isomannide (2) and isoidide (3), and any combination thereof, or may be selected from the group consisting of 4,4′-biphenol, bisphenol A, bisphenol S, hydroquinone, tetramethylbisphenol F, and any combination thereof.
[0189] The aromatic diol monomer (AA) is preferably selected from the group consisting of 4,4'-biphenol, bisphenol A, bisphenol S, isosorbide (1), tetramethylbisphenol F, hydroquinone, and any combination thereof, more preferably selected from the group consisting of 4,4'-biphenol, bisphenol A, bisphenol S, tetramethylbisphenol F, and any combination thereof.
[0190] When the added PAES (P1) is PSU and the intended PAES (P2) is a PSU homopolymer or copolymer, then the selected aromatic diol monomer (AA) most preferably comprises bisphenol-A.
[0191] When the added PAES (P1) is PPSU and the intended PAES (P2) is a PPSU homopolymer or copolymer, then the aromatic diol monomer (AA) most preferably comprises 4,4'-biphenol.
[0192] When the added PAES (P1) is PES and the intended PAES (P2) is a PES homopolymer or copolymer, then the aromatic diol monomer (AA) most preferably comprises bisphenol S.
[0193] When the aromatic dihalogenated monomer (BB) is added to the reactor vessel, the aromatic dihalogenated monomer (BB) may be selected from the group consisting of: 4,4'-difluorodiphenyl sulfone (DFDPS), 4,4'-dichlorodiphenyl sulfone (DCDPS), disulfonated derivatives thereof, and any combination thereof. More preferably, the aromatic dihalogenated monomer (BB) may be selected from the group consisting of: DCDPS, disulfonated DCDPS, and any combination thereof.
[0194] Alkaline salt-forming agent (A) in the reaction medium
[0195] The basic salt-forming agent (A) may be at least one base selected from the group consisting of potassium carbonate (K2CO3), sodium carbonate (Na2CO3), cesium carbonate (Cs2CO3), sodium hydroxide (NaOH), potassium hydroxide (KOH), potassium tert-butoxide and sodium tert-butoxide.
[0196] The alkaline salt-forming agent (A) is preferably at least one base selected from the group consisting of potassium carbonate (K2CO3), sodium carbonate (Na2CO3), sodium hydroxide (NaOH) and potassium hydroxide (KOH), more preferably selected from the group consisting of potassium carbonate (K2CO3), sodium carbonate (Na2CO3) and sodium hydroxide (NaOH).
[0197] The base acts to deprotonate the aromatic diol monomer to form a basic salt of the diol.
[0198] Polar aprotic solvent (S)
[0199] The condensation for preparing PAES (P2) is carried out in a reaction medium (RM) comprising at least one polar aprotic solvent (S). The polar aprotic solvent (S) is preferably selected such that the PAES (P1) in the recycled polymer material is soluble in the solvent.
[0200] The polar aprotic solvent (S) can be selected from the group consisting of: 1,3-dimethyl-2-imidazolidinone (DMI), dimethyl sulfoxide (DMSO), dimethyl sulfone (DMSO2), diphenyl sulfone, diethyl sulfoxide, diethyl sulfone, diisopropyl sulfone, tetrahydrothiophene-1,1-dioxide (commonly known as tetramethylene sulfone or cyclopentane), N-alkyl-2-pyrrolidone (such as N-methyl-2-pyrrolidone (NMP), N-butylpyrrolidone (NBP), N-ethylpyrrolidone (NEP)), N,N′-dimethylacetamide (DMAc), N,N′-dimethylpropylene urea (DMPU), dimethylformamide (DMF), tetrahydrothiophene-1-monoxide, and any combination thereof.
[0201] The polar aprotic solvent (S) is preferably selected from the group consisting of NMP, NBP, NEP, DMF, DMAc, DMI, DMSO, diphenyl sulfone and sulfolane.
[0202] The polar aprotic solvent (S) is more preferably selected from the group consisting of sulfolane, DMSO, DMAc, DMI, NMP, diphenyl sulfone, and any combination thereof; most preferably selected from the group consisting of sulfolane, DMSO, DMAc, NMP, diphenyl sulfone, and any combination thereof.
[0203] Optional co-solvents
[0204] The condensation reaction for preparing PAES (P2) can be carried out in a mixture of a polar aprotic solvent (S) and a co-solvent that forms an azeotropic mixture with water. The co-solvent that forms an azeotropic mixture with water includes aromatic hydrocarbons, such as benzene, toluene, xylene, ethylbenzene, monochlorobenzene, etc. The co-solvent is preferably toluene or monochlorobenzene (MCB). The co-solvent and the polar aprotic solvent (S) that form an azeotropic mixture are typically used in a weight ratio of about 1:10 to about 1:1, preferably about 1:5 to about 1:1. Water is continuously removed from the reaction medium as an azeotropic mixture with the co-solvent that forms an azeotropic mixture, so that a substantially anhydrous condition is maintained during polymerization. After removing the water formed in the reaction, the co-solvent (e.g., chlorobenzene or toluene) that forms an azeotropic mixture is typically removed from the reaction medium by distillation, leaving the PAES (P2) formed in the polar aprotic solvent (S).
[0205] Adding steps in methods
[0206] The various components of the reaction medium (RM) (i.e., recycled polymer material, at least one monomer (M), basic salt-forming agent (A) and polar aprotic solvent (S), optional components such as polar aprotic solvent (S0) and / or co-solvent) can be added simultaneously or sequentially.
[0207] In some embodiments, when at least one monomer (M) includes at least one aromatic diol monomer (AA), the diol (AA) and the alkaline salt-forming agent (A) can be added to the reactor vessel together in the form of an alkaline salt (AAA) of the diol (AA). In this case, the aromatic diol monomer (AA) is mixed with the alkaline salt-forming agent (A) in a polar aprotic solvent (S0) in a container (e.g., a feed tank) separate from the reactor vessel. It may be necessary to heat the mixture of aromatic diol (AA) + alkaline salt-forming agent (A) + solvent (S0) to promote its reaction with the alkaline salt-forming agent (A) (before polycondensation) to form phenolate and / or bisphenolate and generate an alkaline salt of the diol, hereinafter referred to as (AAA). The temperature of the mixture of diol (AA) + reagent (A) + solvent (S0) can be at least ambient temperature, but should not exceed the boiling point of the solvent (S0), preferably 25°C to 300°C. The alkaline salt (AAA) of the diol (AA) is then added to the reactor vessel. After the (bis)phenolate is formed, the alkaline salt (AAA) of the diol (AA) in the solvent (S0) can be dehydrated (to remove the water formed during the formation of the (bis)phenolate) and then added to the reactor vessel. Any of the solvents described herein for the polar aprotic solvent (S) is also suitable for the solvent (S0) used for the ex situ phenolate reaction. The polar aprotic solvent (S0) is preferably selected from the group consisting of sulfolane, DMSO, DMAc, DMI, DMF, NMP, and combinations thereof. The polar aprotic solvent (S0) is preferably the same polar aprotic solvent (S) used in the reaction medium, but is not required. When the polar aprotic solvent (S) and (S0) are the same, they are preferably selected from sulfolane, DMSO, DMI, DMAc, NMP, or any combination thereof.
[0208] In some cases, the recycled polymer material containing PAES (P1) can be added to the reactor vessel in a solid form, such as pellets, fibers, powders, flakes, chopped or ground products, solidified solids (e.g., solidified polymer beads, particles or pellets), any other solid 3-D objects, or any mixture thereof. The pellets can be in any shape, such as cylindrical, spherical or oval. In particular, when the recycled polymer material can include post-industrial waste from a polyarylethersulfone manufacturing plant, such waste can be obtained after the solidification step (in solidified form) and then not dried before recycling and used as a reactant in the current method. The shape and size of the recycled polymer material are not critical, as long as the PAES (P1) in the recycled polymer material can be at least partially, preferably completely dissolved in a polar aprotic solvent.
[0209] In some embodiments, the recycled polymer material comprising PAES (P1) may be added directly to the reactor vessel in solid form, and at least some of the PAES (P1) may be "pre-dissolved" with some or all of the polar aprotic solvent (S) prior to addition of the other components (A) and (M) of the reaction medium (RM). It may be necessary to heat during pre-dissolution in order to facilitate dissolution of the PAES (P1). Dissolution at a temperature of at least ambient temperature may be advantageous, but should not exceed the boiling point of the solvent (S), preferably 50°C to 150°C or 70°C to 130°C.
[0210] In other embodiments, the one or more monomers (M) and the recycled polymer material comprising PAES (P1) may be added directly to the reactor vessel in solid form, and at least a portion of the one or more monomers (M) and PAES (P1) may be "pre-dissolved" with a polar aprotic solvent (S) prior to adding component (A) to the reactor vessel. It may be necessary to heat during pre-dissolution in order to facilitate dissolution of the one or more monomers (M) and PAES (P1). Dissolution at a temperature of at least ambient temperature may be advantageous, but should not exceed the boiling point of the solvent (S), preferably 50°C to 150°C or 70°C to 130°C.
[0211] In an alternative embodiment, a recycled polymer material comprising PAES (P1) can be added to the reactor vessel in the form of a solution or slurry, wherein at least some of the PAES (P1) is "pre-dissolved" off-site (i.e., not in the reactor vessel) and then added to the reactor vessel. In such a case, the recycled polymer material can be mixed with a polar aprotic solvent (S0). It may be necessary to heat the mixture of recycled polymer material + solvent (S0) to promote the dissolution of PAES (P1) in the solvent (S0). Dissolution at a temperature of at least ambient temperature can be advantageous, but should not exceed the boiling point of the solvent (S0), preferably 50°C to 150°C or 70°C to 130°C. This pre-dissolution is preferably carried out in a container (e.g., a feed tank) separate from the reactor vessel. In some cases, when the resulting pre-dissolved material is in the form of a slurry containing solids (e.g., insoluble fillers derived from recycled polymer materials), the solids can be removed (e.g., the slurry is filtered) to recover the PAES (P1) solution. The PAES (P1) solution is then added to the reactor vessel. The polar aprotic solvent (S0) in which PAES (P1) can be pre-dissolved is preferably the same polar aprotic solvent (S) used in the reaction medium, but it is not necessary. This polar aprotic solvent (S0) is particularly selected for its ability to completely dissolve PAES (P1) and optionally one or more monomers (M) when it is mixed with PAES (P1) in an ex situ manner. Any solvent in the solvent described herein for the polar aprotic solvent (S) is also suitable for pre-dissolving PAES (P1) and optionally one or more monomers (M) before adding to the reactor container. The polar aprotic solvent (S0) is preferably selected from the group consisting of sulfolane, DMSO, DMAc, DMI, DMF, NMP, and combinations thereof. When the polar aprotic solvent (S) and (S0) are the same, they are preferably selected from sulfolane, DMSO, DMAc, NMP, or combinations thereof.
[0212] In certain embodiments, the various addition steps for preparing the reaction medium (RM) may be performed as follows:
[0213] - loading the recycled polymer material comprising PAES (P1) into a reactor vessel together with a solvent (S) to dissolve the PAES (P1) in the solvent (S), preferably by heating at a temperature from ambient temperature to below the boiling point of the solvent (S), preferably from 50°C to 150°C or from 70°C to 130°C; and
[0214] - Then after the PAES (P1) is dissolved, at least the monomer (M) and the alkaline salt-forming agent (A) are added to the reactor vessel simultaneously or sequentially. In some cases, when at least the monomer (M) includes an aromatic diol (AA), the diol (AA) and the alkaline salt-forming agent (A) can be added 'as is', or they can be mixed and reacted ex situ in a separate container (e.g., a feed tank) to form a (bis)phenolate and generate an alkaline salt (AAA) of the diol (AA). The resulting alkaline salt (AAA) of the diol (AA) is then added to the reactor vessel. After the (bis)phenolate is formed, the alkaline salt (AAA) of the diol (AA) in the solvent (S0) can be dehydrated (to remove water formed during the formation of the (bis)phenolate) and then added to the reactor vessel.
[0215] In an alternative embodiment, the various addition steps for preparing the reaction medium (RM) may be performed as follows:
[0216] - pre-dissolving the recycled polymer material comprising PAES (P1) with solvent (S) [or if not solvent (S), solvent (S0)] ex situ (i.e. in a feed tank separate from the reactor vessel) to dissolve the PAES (P1) preferably by heating at ambient temperature to a temperature below the boiling point of the solvent (S) (preferably 50°C to 150°C or 70°C to 130°C), and optionally filtering after dissolution to remove solids; and
[0217] - The pre-dissolved PAES (P1), at least the monomers (M), the alkaline salt-forming agent (A) and optionally the solvent (S) [if the solvent (S0) is used for the PAES (P1) pre-dissolution and / or the phenolate formation] are then added simultaneously or successively to the reactor vessel. Similarly, as previously explained, in some cases, when at least the monomers (M) comprise an aromatic diol (AA), the diol (AA) and the alkaline salt-forming agent (A) may be reacted (to form a (bis)phenolate) prior to polycondensation and added to the reactor vessel in the form of an alkaline salt (AAA) of the diol (AA). After the (bis)phenolate formation, the alkaline salt (AAA) of the diol (AA) in the solvent (S0) may be dehydrated and then added to the reactor vessel.
[0218] In yet an alternative embodiment, the various addition steps for preparing the reaction medium (RM) may be performed as follows:
[0219] - loading at least monomers (M) and recycled polymer material comprising PAES (P1) into a reactor vessel together with a solvent (S) to dissolve the one or more monomers (M) and PAES (P1) in the solvent (S), preferably by heating at a temperature from ambient temperature to below the boiling point of the solvent (S), preferably from 50°C to 150°C or from 70°C to 130°C; and
[0220] - The basic salt former (A) is then added to the reactor vessel after the monomer(s) (M) and the PAES (P1) have dissolved.
[0221] Polycondensation reaction steps
[0222] Without wishing to be bound by theory, it is believed that the trans-etherification chemistry effects the disruption of the ether bonds of the repeating units of the recycled polymer PAES (P1) and polymer chains formed from the monomers / oligomers, thereby incorporating them into the final chain of the resulting polymer PAES (P2) formed by the process of the present invention.
[0223] In particular, when the recycling ratio is 100 wt.%, the ether exchange disrupts the ether bonds of the repeating units of the recycled PAES (P1), so that the resulting polymer PAES (P2) is substantially the same in chemical structure (same repeating units) and very similar in properties to the native polymer that would be made from the monomers alone, and therefore, the use of the polymer PAES (P2) should not be limited in any way.
[0224] Similarly, when the monomers added to the reaction medium (RM) and favoring the formation of new polymer chains correspond to the same monomers from which the recycled PAES (P1) is derived, the resulting polymer PAES (P2) will also be identical in chemical structure (same repeating units) and have very similar properties as the virgin polymer obtained directly from these added monomers, for example, the process may comprise using recycled PES waste material and adding bisphenol S and DCDPS to the reactor vessel to form a new PES polymer (P2) comprising PES repeating units having formula (O).
[0225] On the other hand, when the monomers added to the reaction medium (RM) favor the formation of new polymer chains of different types of sulfone polymers, the resulting polymer PAES (P2) will differ in chemical structure compared to the recycled PAES (P1) because the PAES (P2) will contain the same repeating units as the PAES (P1) but also different repeating units resulting from the condensation of the added monomers. In this case, the resulting PAES (P2) will likely differ in some properties when compared to the recycled PAES (P1) and the virgin polymer that would be obtained with the monomers added to the reaction medium (RM) in the absence of recycled (P1). For example, the method may include using recycled PES waste material and adding biphenol and DCDPS to the reactor vessel to form a new copolymer having not only PES repeating units having formula (O) but also some PPSU repeating units having formula (Q).
[0226] The main advantage of the process according to the invention is that it comprises a one-pot synthesis (in the same reactor vessel) from recycled polymer material containing PAES (P1) used as reactant. The polymer material containing PAES (P1) is preferably added to the reaction medium before the start of the polycondensation.
[0227] Thus, before the start of polycondensation, the reaction medium (RM) in the reactor vessel comprises a polymer recycle material containing PAES (P1), at least one monomer (M), a basic salt-forming agent (A) and a polar aprotic solvent (S).
[0228] The reaction medium (RM) may further contain a polar aprotic solvent (S0) for predissolving the PAES (P1) and / or an azeotrope-forming cosolvent, as described previously.
[0229] When the at least one monomer (M) comprises at least one aromatic diol monomer (AA), the reaction medium (RM) comprises the following molar ratio of the basic salt-forming agent (A) to the aromatic diol monomer (AA):
[0230] - at least 0.95:1, at least 0.98:1, at least 0.99, at least 0.995, or at least 1:1; and / or
[0231] - at most 2.5:1, at most 2.2:1, at most 2:1, at most 1.8:1, at most 1.6:1, at most 1.4:1; at most 1.35:1 or at most 1.3:1.
[0232] When the at least one monomer (M) comprises at least one aromatic diol monomer (AA) and at least one aromatic dihalide monomer (BB), the reaction medium (RM) comprises a molar ratio of one or more aromatic dihalide monomers (BB) / one or more aromatic diol monomers (AA) of at least 0.9: 1, at least 0.92: 1, at least 0.95: 1, at least 0.98: 1, at least 0.99, at least 0.995, or at least 1: 1; and / or at most 1.1: 1, at most 1.08: 1, at most 1.07: 1, at most 1.06: 1; at most 1.05: 1 or at most 1.04: 1. Preferred molar ratios of one or more aromatic dihalide monomers (BB) / one or more aromatic diol monomers (AA) are 0.95 to 1.05, or 0.98 to 1.02, or 0.99 to 1.01.
[0233] During the reaction time, the reaction medium (RM) preferably contains 5 wt.% to 40 wt.%, 10 wt.% to 35 wt.%, 5 wt.% to 40 wt.%, 15 wt.% to 35 wt.%, 20 wt.% to 35 wt.%, or 20 wt.% to 30 wt.% of PAES polymers ((P1) and (P2)), based on the total weight of the reaction medium.
[0234] The reaction time may be 2 to 20 hours, preferably 3 to 12 hours, more preferably 3 to 10 hours, still more preferably 3.5 to 8 hours, most preferably 3.5 to 6 hours.
[0235] The reaction temperature for forming PAES (P2) is at least 150° C. The reaction temperature is preferably at least 160° C., at least 165° C., at least 170° C., at least 175° C., at least 180° C., at least 185° C., at least 190° C., at least 195° C., or at least 200° C.; and / or at most 350° C., at most 300° C., at most 295° C., at most 290° C., at most 285° C., at most 280° C., at most 275° C., at most 270° C., at most 265° C., or at most 260° C. Preferred ranges may be from about 150° C. to about 350° C., from about 160° C. to about 350° C., from about 160° C. to about 295° C., from about 160° C. to about 290° C., from about 165° C. to about 285° C., or from about 170° C. to about 280° C.
[0236] Recirculation ratio
[0237] A recycled polymer material containing PAES (P1) can be added to the reaction medium to achieve a PAES (P1) recycling ratio of 100 wt.% to 1 wt.%, preferably 100 wt.% to 5 wt.%. Such a recycling ratio is the ratio of the weight of the added PAES (P1) to the combined weight of the maximum weight of the added PAES (P1) and the additional polymer that would theoretically result from the polycondensation of the monomers (AA) and (BB) based on equimolar stoichiometry when both the diol monomer (AA) and the dihalogenated monomer (BB) are added to the reaction medium.
[0238] For example, when 1.015 moles of biphenol and 1 mole of DCDPS are added to the reaction medium, equal molar amounts of biphenol (diphenol AA) and DCDPS (dihalogenated BB) are required due to polycondensation to produce a PPSU repeating unit having formula (Q):
[0239]
[0240] Therefore, a maximum of 1 mol of polycondensed PPSU can be formed from these monomers (AA) and (BB). Since the PPSU repeating unit having formula (Q) has a molecular weight of 400 g / mol, a maximum of 400 g of PPSU polymer can be produced from 1.015 mol of diphenol (diphenol AA) and 1 mol of DCDPS (dihalogenated BB). In this case, when 40 g of recycled PPSU is added to the reaction medium as PAES (P1), the PPSU recycling ratio will be 40 g / (40 g+400 g)=9 wt.%. On the other hand, when 400 g of recycled PPSU is added as PAES (P1) to a reaction medium containing 0.1015 mol of diphenol and 0.1 mol of DCDPS (to generate a maximum of 40 g of PPSU), the PPSU recycling ratio will be 400 g / (400 g+40 g)=90.9 wt.%. When only recycled PPSU and diphenol (without DCDPS) are added to the reaction medium, the PPSU recycling ratio is 100 wt.%.
[0241] The same type of calculation can be used for:
[0242] - PES formed from bisphenol S and DCDPS (as monomers AA and BB, respectively), wherein the PES repeating unit has a molecular weight of 464 g / mol, or
[0243] - PSU produced from bisphenol A and DCDPS (as monomers AA and BB, respectively), wherein the PSU repeating unit has a molecular weight of 442 g / mol.
[0244] In another way, once the recycle ratio is selected, the number of moles of monomers (AA) and (BB) to be added can be calculated. For example, in the case where "m1" g of PAES (P1) is added to the medium (RM) and a given recycle ratio "z" is desired (for 1 wt.% to 100 wt.%, 0.01 to 1 is used), then the amount of polymer "y" that can be produced from monomers AA and BB is calculated as follows: y = (m1-z m1) / z. When m1 = 400 g of PES is added and a recycle ratio of 40 wt.% (z = 0.4) is desired, then 600 g of PES can be produced or 600 / 464 = 1.293 moles of PES are produced. Therefore, 1.293 moles of DCDPS are used, while 1.293 moles or more of bisphenol S can be used.
[0245] In some cases, when no aromatic dihalide (BB) or no aromatic diol (AA) is added to the reaction medium, it will be impossible to generate new polymer chains from at least the monomer (M) because one of the monomers (AA) and (BB) is not present in the reaction medium. Therefore, the recycling ratio of PAES (P1) in this method is 100 wt.%.
[0246] Separation step in the method for recovering PAES (P2)
[0247] At the end of the reaction, PAES (P2) is separated from the other components of the reaction medium. The separated PAES (P2) can be in the form of a PAES (P2) solution or in solid form (such as solidified or dried).
[0248] Non-polymer components (e.g. sodium chloride or potassium chloride or excess base) as well as non-polymer fillers originating from the starting recycled polymer material can be removed from the reaction medium before or after separation of the PAES (P2) by suitable methods such as dissolution and filtration, screening or extraction.
[0249] The separated PAES (P2) can first be recovered in the form of a PAES (P2) solution. This step can include filtering the reaction medium to remove solid components and recovering the PAES (P2) solution. The PAES (P2) solution should contain PAES (P2) dissolved in a solvent (S) (used during the condensation) and optionally a solvent (SO).
[0250] The PAES (P2) is preferably recovered in solid form from the solvent (S) and optionally the solvent (S0) (if used for the pre-dissolution of the PAES (P1)). This step may include filtering the reaction medium to remove solid components (such as alkali metal salts and / or insolubles from recycled polymer materials) and recovering the PAES (P2) solution. In some embodiments, when a 100 wt.% recycling ratio is used (meaning that the polymer chains of the resulting PAES (P2) grow from depolymerized PAES (P1)), not much alkali metal salt should be formed during the reaction, and the filtering step can be omitted in the method of the present invention.
[0251] In order to recover PAES(P2) in solid form, the PAES(P2) solution may be preferably precipitated from the PAES(P2) solution by coagulation or the one or more solvents may be removed from the PAES(P2) solution.
[0252] Solidification is based on the precipitation of PAES (P2) with a non-solvent or a poor solvent. The solidification step is preferably carried out by forming the droplets of the PAES (P2) solution into a precipitation bath containing a non-solvent or a poor solvent to form polymer beads of PAES (P2). The non-solvent can be selected from C1-C5 alcohols (such as methanol, ethanol, n-propanol, isopropanol, butanol), ethyl acetate, methyl acetate, acetone, butanone, water, or any mixture thereof. Preferred non-solvents include ethanol, methanol, water, or any mixture thereof. The poor solvent can be a mixture of a non-solvent and a solvent (S) and / or (S0). The non-solvent or the poor solvent can contain at least 50wt.%, preferably at least 60wt.% of water and / or C1-C5 alcohols such as methanol or ethanol.
[0253] The recovered solid PAES (P2) can be subjected to one or more washings with washing liquids to further remove salts or other components retained in the polymer solids. The washing liquid is preferably water and / or a C1-C5 alcohol (e.g., methanol, ethanol, n-propanol, isopropanol). The washing liquid (e.g., water) is preferably at a temperature of at least 50°C or at least 60°C or at least 65°C. The washing liquid should be at a temperature not exceeding its boiling point. The washing liquid is preferably at a temperature of at most 90°C or at most 85°C or at most 80°C or at most 75°C. The washing liquid is more preferably water at a temperature of 60°C to 80°C or 65°C to 75°C. Two or more washings can be performed using different washing liquids, such as first washing with water one or more times and then washing with methanol one or more times.
[0254] Solid PAES (P2) can be dried at a temperature of typically about 50 to 120°C, preferably about 80 to 120°C, more preferably about 90-120°C, still more preferably about 90-110°C, preferably under vacuum.
[0255] The dried PAES (P2) can be used to prepare articles such as but not limited to fibers, sheets, films or membranes.
[0256] Optional steps in methods
[0257] The method according to the present invention may further comprise at least one of the following steps between the reaction (condensation) step and the separation step:
[0258] i. Cooling: lowering the temperature of the reaction medium;
[0259] ii. Quenching: Addition of a solvent (S) which may be the same as or different from the polar aprotic solvent (S) q ) to quench the reaction medium, generally to stop the reaction and dilute the reaction medium to reduce its viscosity; and / or
[0260] iii. End-capping: An end-capping agent is added to convert the hydroxyl end groups of the formed PAES (P2) into less reactive end groups.
[0261] In some embodiments of the method according to the invention, only one optional step may be performed.
[0262] Alternatively, at least two optional steps are performed.
[0263] Step (i): cooling can be affected by stopping the heating of the reaction medium. Cooling can be achieved by adding another amount of polar aprotic solvent (S) or another solvent directly to the reaction medium, the other solvent being at a temperature at least 50°C, at least 60°C, or at least 70°C lower than the reaction medium temperature. The solvent added to the reaction medium for cooling is preferably at ambient temperature. The solvent added for cooling is preferably selected from the group consisting of: sulfolane, DMSO, DMAc, DMI, NMP, MCB, and any combination thereof. Alternatively, cooling can be affected by passing a cooling fluid (not mixed with the reaction medium (RM)) inside a cooling tube or using a cooling jacket for the reactor vessel.
[0264] Step (ii): Quenching can be carried out at the end of the reaction to reduce the polymer content of the reaction medium to a value of 20 wt.% or less based on the total weight of the quenched reaction medium. The solvent (S) added for quenching q ) is preferably the same as the polar aprotic solvent (S) used during the reaction, but is not required. q ) is preferably selected from the group consisting of sulfolane, DMSO, DMAc, DMI, NMP, MCB, and any combination thereof. After quenching, the polymer content of the quenched reaction medium is preferably 5 wt.% to 20 wt.%, more preferably 10 wt.% to 15 wt.%, based on the total weight of the quenched reaction medium.
[0265] The cooling and quenching steps (i) and (ii) can be performed at the end of the reaction by using a solvent (S) having a temperature cooler than the reaction temperature of the reaction medium. q ) simultaneously.
[0266] Step (iii): Capping (also referred to as termination) preferably converts the reactive hydroxyl end groups of the PAES (P2) formed into less reactive end groups. The end-capping agent is preferably methyl chloride ("MeCl"). Chloromethyl gas may be passed through the reaction medium. The end-capping step (iii) may be carried out before or after cooling of the reaction medium. Thus, the end-capping step (iii) may be carried out at the reaction temperature or at a temperature lower than the reaction temperature at the end of the polycondensation reaction. If it is desired to obtain a final PAES (P2) product having reactive (-OH) end groups, the end-capping step (iii) is preferably omitted in the process of the present invention.
[0267] Application of PAES(P2)
[0268] Another aspect of the present invention provides the use of PAES (P2) for the preparation of an article (or a part thereof) as described herein.
[0269] Method for preparing an article
[0270] Another aspect of the present invention provides a method for preparing or making an article (or a portion thereof) comprising PAES(P2). The method for making the article may comprise using PAES(P2) in forming the article or a portion thereof.
[0271] The article may be formed from a solution comprising PAES (P2).
[0272] When the article is a membrane or a portion thereof, the method may include effecting a phase inversion in a liquid phase (eg, a precipitation bath) to form the membrane or a portion thereof from a solution containing PAES (P2).
[0273] The method may involve solution spinning techniques.
[0274] Products containing PAES(P2)
[0275] Another aspect of the present invention provides an article (preferably a shaped article) comprising a PAES (P2) according to the present invention.
[0276] The article can be an injection molded article, an extruded article, a pultruded article, or a solution processed article (eg, solution cast).
[0277] The article comprising PAES(P2) may be selected from the group consisting of: a film (eg, a solution cast film); a fiber; a sheet; a solution processed membrane (eg, a porous film); and a solution processed monofilament.
[0278] PAES (P2) can be incorporated into an article having a polymer surface. The article can have a polymer surface, at least a portion of which is in direct contact with an aqueous medium such as water, an aqueous solution, a biological fluid, and / or a food product in its intended application setting. The polymer surface can be the outer surface or the inner surface of the article. For example, a medical device has an outer surface intended to be in direct contact with a biological fluid (such as blood, plasma, or serum). One of ordinary skill in the art will know which surface is intended to contact a biological fluid or a food product based on the intended application setting of the article.
[0279] As another example, the surface of the article may include a coating or film comprising PAES(P2) disposed on an underlying substrate. In such an embodiment, the underlying substrate may be a structural component having a composition different from that of PAES(P2).
[0280] In embodiments where the PAES (P2) is in a thin film, the thin film may have an average thickness of about 25 μm to about 1 mm.
[0281] PAES (P2) may be included in at least a portion of the surface of the article, which is intended to contact this surface with a biological fluid such as blood, plasma or serum. Alternatively, PAES (P2) may form all or substantially all of the article.
[0282] The shaped article comprising PAES (P2) can preferably be a membrane or a part thereof selected from the following: proton exchange membranes, membranes for bioprocessing (e.g., enzyme or cell culture filtration), membranes for medical filtration (e.g., hemodialysis membranes), membranes for food and beverage processing, membranes for water purification, membranes for wastewater treatment, and membranes for separation in industrial processes involving aqueous media.
[0283] Among membranes, the PAES (P2) according to the invention is particularly suitable for the manufacture of membranes intended to be in contact with aqueous media. The aqueous media may include biological fluids such as blood, or food products such as beverages (eg juice, milk).
[0284] From an architectural standpoint, membranes comprising PAES(P2) can be provided in the form of flat structures (e.g., films or sheets), corrugated structures (e.g., corrugated sheets), tubular structures, or hollow fibers; in terms of pore size, PAES(P2) can advantageously be used to make a variety of membranes (non-porous and porous, including for microfiltration, ultrafiltration, nanofiltration, and reverse osmosis); the pore distribution can be isotropic or anisotropic.
[0285] Among the applications of use, mention may be made of healthcare applications, in particular medical applications, wherein shaped articles comprising PAES(P2) may advantageously be used in disposable and reusable instruments and devices.
[0286] Among the applications of use, mention may be made of fuel cell applications, where PAES(P2) may advantageously be used in proton exchange membranes.
[0287] The article may comprise PAES (P2) and optionally another sulfone polymer different from PAES (P2) in an amount ranging from 1 wt.% to 99 wt.%, for example 2 wt.% to 98 wt.%, 3 wt.% to 97 wt.%, or 4 wt.% to 96 wt.%, based on the total weight of the polymer. In such a case, when the article comprises PAES (P2) and another sulfone polymer such as virgin PSU, PES and / or PPSU, the weight fraction of PAES (P2) based on the combined weight of PAES (P2) and the other sulfone polymer(s) in the article is at least 10 wt.%, or at least 15 wt.%, or at least 20 wt.%, or at least 25 wt.%, and / or up to 99 wt.%, or up to 98 wt.%, or up to 96 wt.%, or up to 95 wt.%, or up to 90 wt.%.
[0288] Membrane or film (as product)
[0289] The article may be a film or membrane, or a portion thereof.
[0290] A particular embodiment of the article, preferably a shaped article, relates to a membrane comprising PAES (P2). The membrane may be used for proton exchange or for purifying water, food products or biological fluids, such as blood.
[0291] An embodiment of the membrane according to the invention relates to a proton exchange membrane comprising PAES (P2).
[0292] Another embodiment of the membrane according to the invention relates to a purification membrane comprising PAES(P2), such as for purifying water, food products or biological fluids, such as blood.
[0293] The membrane may be a microporous membrane, which may be characterized by its average pore size and porosity (ie, the fraction of the entire membrane that is porous).
[0294] The membrane may have a weight porosity (%) of 20% to 90% and comprise pores wherein at least 90% by volume of the pores have an average pore size of less than 5 μm. The weight porosity of the membrane is defined as the volume of the pores divided by the total volume of the membrane.
[0295] Membranes with a uniform structure throughout their thickness are generally referred to as symmetric membranes; membranes with pores that are non-uniformly distributed throughout their thickness are generally referred to as asymmetric membranes. Asymmetric membranes are characterized by a thin selective layer (0.1-1 μm thick) and a highly porous thick layer (100-200 μm thick) that acts as a support and has little effect on the separation characteristics of the membrane.
[0296] The membrane may be in the form of a flat sheet or in the form of a tube.
[0297] The membrane may be formed using a plurality of thin films or fibers.
[0298] Tubular membranes are classified based on their size into tubular membranes with a diameter greater than 3 mm, capillary membranes with a diameter comprised between 0.5 mm and 3 mm, and hollow fibers with a diameter less than 0.5 mm. Capillary membranes are otherwise known as hollow fibers.
[0299] Hollow fibers are particularly advantageous in applications requiring compact modules with high surface area.
[0300] The membrane, fiber or film according to the present invention can be manufactured using any of the conventionally known membrane, fiber or film preparation methods. For example, the film preparation method can use a solution casting method.
[0301] The membrane or film according to the present invention can be prepared by a phase inversion method occurring in a liquid phase, the method comprising the steps of preparing a polymer solution comprising the PAES (P2) described herein and a polar solvent, processing the polymer solution into a film; and contacting the film with a non-solvent bath.
[0302] The present invention will now be described in more detail with reference to the following examples, the purpose of which is merely illustrative and not limiting the scope of the present invention.
[0303] Examples
[0304] The present invention will now be described in more detail with reference to the following examples, the purpose of which is merely illustrative and does not limit the scope of the present invention.As used in the examples, "E" represents an embodiment of the present invention, and "CE" represents a counterexample.
[0305] GPC Method for Measuring Mn, Mw ("Sulfone GPC Method #1")
[0306] Molecular weights were measured by gel permeation chromatography (GPC) using dichloromethane as the mobile phase. Two 5 μ mixed D columns with guard columns from Agilent Technologies were used for separation. Chromatograms were obtained using a UV detector at 254 nm. A flow rate of 1.5 ml / min and an injection volume of 20 μL of a 0.2 w / v% solution in the mobile phase were selected. Calibration was performed with 10 or 12 narrow molecular weight polystyrene standards. Number average molecular weight Mn and weight average molecular weight Mw were reported, and PDI=Mw / Mn was calculated.
[0307] Example 1: PES recycling
[0308] Raw materials for samples E1-E2, CE3, CE4, E5
[0309] Na2CO3 (sodium carbonate), available from Solvay France DCDPS (4,4'-dichlorodiphenyl sulfone), available from Solvay Speciality Polymers
[0310] DHDPS (4,4'-dihydroxydiphenyl sulfone or bisphenol S), available from Sigma-Aldrich
[0311] Sulfolane, available from ChevronPhillips Chemicals
[0312] Methyl chloride, available from Matheson Gas
[0313] Methanol, available from Sigma-Aldrich
[0314] PES1: 3000MP PES, manufactured by Solvay Specialty Polymers, with Mw = 64,145; Mn = 19,145; PDI = 3.35
[0315] Synthesis of PES samples E1-E2: PES polymerization process using 20 wt.% added PES as reactant
[0316] To prepare PES samples E1 and E2, firstly, monomer DHDPS and 1 mol.% excess (relative to the amount of DHDPS) of DCDPS (meaning the molar ratio of DCDPS / DHDPS is 1.01) and 3000MP (PES1) was added to a 1.0-L glass reactor vessel equipped with an overhead stirrer and a nitrogen inlet. Sodium carbonate was then added to achieve an 18% molar excess of Na2CO3 (relative to the amount of DHDPS), which means that the molar ratio of Na2CO3 / DHDPS was 1.18. The reaction medium was heated from room temperature to 227+ / -2°C in 90min. The polymerization temperature of the reaction medium was maintained for about 3.6 to 4.1 hours, depending on the viscosity of the solution. The polymerization was carried out in the reaction medium at a polymer concentration of 26.4wt.%. The reaction was terminated by adding methyl chloride (about 1g / min) and re-capping the polymer at 227±2°C for 30 minutes. The reaction medium was quenched by diluting with sulfolane to achieve a polymer content of 15wt.%. Therefore, termination was performed at the polymerization temperature (227°C) and then quenched with additional sulfolane. After quenching, the reaction medium was filtered through a 2.7-μm glass fiber filter pad under nitrogen pressure and coagulated into water using a high-speed Waring blender at a polymer solution / water volume ratio of 1:5. The coagulated polymer was then washed five times with hot water (70° C.) and dried overnight in an oven at 110° C. under vacuum.
[0317] The difference between samples E1 and E2 is that the polymerization of sample E1 was terminated earlier (3.6 hours) than the polymerization of sample E2 (4.1 hours).
[0318] Synthesis of sample CE3 (counterexample) - PES polymerization process (without using PES as a reactant)
[0319] For sample CE3, polymerization was carried out in the same manner as described above for samples E1 and E2, except that no PES was added to the reaction medium and the reaction time was 4.6 hours.
[0320] exist The Mw, Mn and PDI (via sulfone GPC method) of the PES polymers produced after coagulation and drying in samples E1, E2 and CE3 are reported in .
[0321] It was observed that when the reaction times were similar, the resulting polymer with added 20 wt.% PES1 as a reactant in sample E2 had similar Mw and Mn values as CE3 without PES1 reactant.
[0322] For sample E2, there is a small decrease in Mw (-7%) relative to control sample CE3. This is in contrast to sample E1 which loses 35% of Mw relative to control CE3 due to the shorter reaction time.
[0323] There is also a decrease in the PDI values of samples E1 (-25%) and E2 (-18%) relative to the control sample CE3.
[0324] Synthesis of Sample E4: PES polymerization process using 10 wt.% PES1 recycling
[0325] Polymerization was carried out in the same manner as described for sample E2, except that after washing five times with hot water (70°C), the coagulated polymer of sample E4 was further washed once with methanol. Additionally, sample E4 was formed using only 10 wt.% PES1 (compared to 20 wt.% PES1 in samples E1 and E2).
[0326] Synthesis of sample CE5 (counterexample) - PES polymerization process (without PES addition)
[0327] The polymerization to form sample CE5 was carried out in the same manner as described for sample CE3, except that after washing five times with hot water (70° C.), the coagulated polymer was further washed once with methanol to produce PES sample CE5.
[0328] Still The Mw, Mn and PDI (via sulfone GPC method) of the PES polymers produced after coagulation and drying in samples CE4 and E5 are reported in .
[0329] Table 1
[0330]
[0331] **Sulfone GPC Method #1 using dichloromethane as mobile phase
[0332] It was observed that when the reaction conditions (including reaction time) were similar, the resulting PES with added 10 wt.% PES1 as reactant in sample E4 had similar Mw and Mn values as sample CE5 without added PES1.
[0333] For sample E4, there is a small decrease in Mw (-10%) relative to control sample CE5, and there is also a small decrease in PDI value (-8%) relative to control sample CE5.
[0334] Example 2 - PES Recycling
[0335] GPC method for measuring Mn and Mw
[0336] The same sulfone GPC method #1 as described above was used.
[0337] Raw materials for samples E6-E12 and CE13
[0338] Na2CO3 (sodium carbonate), available from Solvay
[0339] DCDPS (4,4'-dichlorodiphenyl sulfone), available from Solvay Specialty Polymers DHDPS (4,4'-dihydroxydiphenyl sulfone or bisphenol S), available from Sigma-Aldrich
[0340] Sulfolane, available from Chevron Phyllis Chemical Company
[0341] PES2: 3300PES, manufactured by Solvay Specialty Polymers, has Mw = 45249; Mn = 15244; PDI = 2.97; in powder form
[0342] PES3: 3000MP PES, manufactured by Solvay Specialty Polymers, having Mw = 67559; Mn = 18013; PDI = 3.75; in powder form
[0343] PES4: 3300PES, manufactured by Solvay Specialty Polymers, having Mw = 45735; Mn = 14785; PDI = 3.09; in pellet form
[0344] Synthesis of PES sample E6 -PES manufacturing using 100 wt.% PES powder recycling
[0345] PES2 powder (Mw = 45249) (232g) was loaded into a 1.25 liter glass polymerization reactor together with 460ml of sulfolane. The reaction medium was heated at 50RPM under stirring in a continuous nitrogen flow. After the polymer was partially dissolved at about 100°C, 4,4'-dihydroxydiphenyl sulfone (DHDPS) (2.5g, 0.01mol) and sodium carbonate (6.0g, 0.0566mol) were added to the reaction medium. The stirring speed was increased to 200RPM. The reaction medium was heated at 227°C for 3.5 to 4 hours. The molecular weight growth of the polymerization was monitored via GPC. The polymerization reaction was quenched by adding 250ml of sulfolane. Subsequently, methyl chloride was purged through the reaction medium to terminate the polymer chain for 30 minutes. The reaction medium was subjected to coagulation in 1.5 liters of deionized water in a Waring blender to obtain a coagulated polymer. In an Ace Glass The coagulated polymer was washed with cold and hot water in an extraction kettle until the residual solvent content was reduced to about 0.3 wt.%. The washed polymer powder was dried at 120° C. for 24 hours. A dry PES polymer (sample E6) with a mass of 212 g was obtained with a yield of about 91%.
[0346] Synthesis of PES sample E7 - PES manufacturing using 30 wt.% PES powder recycling
[0347] DCDPS (102.459 g, 0.357 mol), DHDPS (87.5 g, 0.35 mol) and PES3 powder (Mw=67559) (69.6 g) were loaded into a 1.25 liter glass polymerization reactor together with 460 ml of sulfolane. The reaction medium was heated at 200 RPM in a continuous nitrogen stream under stirring. After the monomer was dissolved at about 70° C., sodium carbonate (47.908 g, 0.413 mol) was added to the reaction medium. The reaction medium was heated at 227° C. for 4 hours. The molecular weight growth of the polymerization was monitored via GPC. The polymerization reaction was quenched by adding 250 ml of sulfolane. Subsequently, methyl chloride was purged through the reaction medium to terminate the polymer chain for 30 minutes. The reaction medium was then pressure filtered using an Advantec filtration system through a 2.7 micron glass fiber filter pad. The filtered reaction medium was subjected to coagulation in 1.5 liters of deionized water in a Waring blender to obtain a coagulated polymer. The coagulated polymer was washed with cold and hot water in an extraction kettle until the residual solvent content was reduced to about 0.3 wt.%. The washed polymer solid was dried at 120° C. for 24 hours. A dry PES polymer powder (sample E7) with a mass of 189 g was obtained with a yield of about 81%.
[0348] Synthesis of PES samples E8a and E8b -PES manufacturing using 50wt.% PES powder chemical recycling
[0349] DCDPS (73.185 g, 0.255 mol) and DHDPS (62.5 g, 0.25 mol), PES3 powder (Mw=67559) (116 g) were loaded into a 1.25 liter glass polymerization reactor along with 460 ml of sulfolane. The reaction medium was heated at 200 RPM under stirring in a continuous nitrogen stream. After the monomers were dissolved at about 70° C., sodium carbonate (31.27 g, 0.295 mol) was added to the reaction medium. The remaining procedure was similar to Example 6 to obtain 196 g of dry PES polymer (sample E8a) with a yield of about 84%.
[0350] The procedure was repeated under the same conditions as described above, except using a slightly different reaction time, to produce another dried PES sample E8b.
[0351] Synthesis of PES samples E9a and E9b -PES manufacturing using 70wt.% PES powder chemical recycling
[0352] DCDPS (43.911 g, 0.153 mol), DHDPS (37.5 g, 0.15 mol) and PES3 powder (Mw = 67559) (162.4 g) were loaded into a 1.25 liter glass polymerization reactor along with 460 ml of sulfolane. The remaining procedure was similar to Example 6 to produce 186 g of dry PES polymer (sample E9a) with a yield of about 80%.
[0353] The procedure was repeated under the same conditions as described above for sample E9a, except using a slightly different reaction time, to produce another dried PES sample E9b.
[0354] Synthesis of PES samples E10a and E10b -PES manufacturing using 90wt.% PES powder chemical recycling
[0355] DCDPS (14.637 g, 0.051 mol) and DHDPS (12.5 g, 0.05 mol), PES3 powder (Mw=67559) (208.8 g) were loaded into a 1.25 liter glass polymerization reactor along with 460 ml of sulfolane. The reaction medium was heated at 50 RPM under stirring in a continuous stream of nitrogen. After the monomers and PES3 powder were dissolved at about 90° C., sodium carbonate (6.254 g, 0.059 mol) was added to the reaction medium. The stirring speed was increased to 200 RPM. The reaction medium was heated at 217° C. for 3 to 4 hours. The molecular weight growth of the polymerization was monitored via GPC. The remaining procedure was similar to Example 7 to produce 208 g of a dry PES polymer sample E10a with a yield of about 89%.
[0356] The procedure was repeated under the same conditions as described above, except using a slightly different reaction time, to produce another dried PES sample E10b.
[0357] Synthesis of PES sample E11 -PES manufacturing using 95wt.% PES powder chemical recycling
[0358] DCDPS (7.318 g, 0.0255 mol), DHDPS (6.25 g, 0.025 mol) and PES3 powder (Mw = 67559) (208.8 g) were loaded into a 1.25 liter glass polymerization reactor together with 460 ml of sulfolane. The reaction medium was heated at 50 RPM under stirring in a continuous nitrogen stream. After the monomers and PES3 powder were dissolved at about 90° C., sodium carbonate (6.254 g, 0.059 mol) was added to the reaction medium. The remaining procedure was similar to Example 7 to obtain 206 g of dry PES polymer (sample E11) with a yield of about 88%.
[0359] Synthesis of PES sample E12 -PES manufacturing using 100 wt.% PES pellet chemical recycling
[0360] PES4 pellets (Mw = 45735) (232g) were loaded into a 1.25 liter glass polymerization reactor along with 460ml of sulfolane. The reaction medium was heated at 20RPM under stirring in a continuous nitrogen stream. After the PES4 pellets were partially dissolved at about 130°C, DHDPS (2.5g, 0.01mol) and sodium carbonate (6.0g, 0.0566mol) were added to the reaction medium. The stirring speed was slowly increased to 200RPM. The reaction medium was heated at 227°C for 3 to 4 hours. The molecular weight growth of the polymerization was monitored via GPC. The polymerization reaction was quenched by adding 250ml of sulfolane. Subsequently, methyl chloride was purged through the reaction medium to cap the polymer chain ends for 30 minutes. The reaction medium was subjected to coagulation in 1.5 liters of deionized water in a Waring blender to obtain a coagulated polymer. In an Ace Glass The coagulated polymer was washed with cold water (30° C.) and hot water (80° C.) in an extraction kettle until the residual solvent content was reduced to about 0.3 wt.%. The washed polymer solid was dried at 120° C. for 24 hours. A dry PES sample E12 with a mass of 208 g was obtained with a yield of about 89%. PES sample CE13 (reverse Example) Synthesis -PES manufacturing without PES recycling
[0361] DCDPS (146.37 g, 0.51 mol) and DHDPS (125 g, 0.50 mol) were loaded into a 1.25 liter glass polymerization reactor together with 460 ml of sulfolane. The reaction medium was heated under stirring at 50 RPM in a continuous nitrogen stream. After the monomers were dissolved at about 70 ° C, sodium carbonate (63 g, 0.59 mol) was added to the reaction medium. The stirring speed was increased to 200 RPM. The reaction medium was heated at 227 ° C for 3 to 4 hours. The remaining procedures were similar to Example 7 to produce 197 g of dry PES sample CE13 with a yield of about 84.9%.
[0362] exist The Mw, Mn and PDI (via sulfone GPC method #1 as described above) of PES samples E6 to E12 and CE13 produced after coagulation and drying are reported in.
[0363] Table 2
[0364]
[0365] **Sulfone GPC Method #1 using dichloromethane as mobile phase
[0366] For PES samples E7-E12, there is only a small change in Mw (from -4.2% to 7.1%) relative to control sample CE13. There is also a slight increase in PDI values from 2.4% to 9.9% relative to control sample CE13.
[0367] Example 3: PES Recycling
[0368] GPC method for measuring Mn and Mw
[0369] The same sulfone GPC method #1 as described above was used.
[0370] Raw materials used for samples E14 and E15
[0371] Na2CO3 (sodium carbonate), available from Solvay
[0372] DHDPS (4,4'-dihydroxydiphenyl sulfone or bisphenol S), available from Sigma-Aldrich
[0373] Sulfolane, available from Chevron Phyllis Chemical Company
[0374] PES5: E020 PES, manufactured by BASF, with Mw = 66842 g / mol; Mn = 20205 g / mol; PDI = 3.3, in the form of flakes
[0375] Synthesis of sample E14 - PES production using 100 wt.% PES pellet recycling
[0376] 40 g of PES5 powder (Mw = 66842) was slowly added to a 250 ml four-necked round-bottom flask containing 80 ml of cyclopentane. The reaction medium was heated at 50 RPM under stirring in a continuous nitrogen stream. After the PES5 polymer was completely dissolved, the stirring speed was increased to 200 RPM. Once the reaction temperature reached 220 ° C, 4,4'-dihydroxydiphenyl sulfone (DHDPS) (0.431 g, 1.7 mmol) and sodium carbonate (0.91 g, 8.5 mmol) were added to the reaction medium. The reaction medium was heated at 227 ° C for about 3.5 h. The molecular weight growth of the polymerization was monitored via GPC (with dichloromethane as the mobile phase). First, the PES5 polymer was depolymerized from Mw-66842 Da to Mw-34490 Da, and then polymerized to a molecular weight Mw of 44258 Da. The polymerization reaction was quenched by adding about 45 ml of cyclopentane. Subsequently, MeCl was purged through the reaction medium to terminate the polymer chains for 30 minutes. The reaction mass was coagulated in 1.2 liters of deionized (MilliQ) water in a Waring blender. The resulting poly(arylene ether) polymer powder was extracted with cold and hot water in an extraction kettle until the residual solvent level dropped to less than about 0.3 wt. %. The polymer powder was dried at 120° C. for 24 hours.
[0377] exist The Mw, Mn and PDI of the resulting PES polymer sample E14 after coagulation and drying are reported in and compared to the starting PES material: PES5 that was added to the reaction medium to make sample E14.
[0378] Table 3
[0379]
[0380] **Sulfone GPC Method #1 using dichloromethane as mobile phase
[0381] For sample E14, which has nearly 100% PES recycle, there is a decrease in Mw (-34%) relative to the initial PES5 polymer. There is also a very small increase in the PDI value of 3% relative to the PES5 polymer.
[0382] Example 4: PES-based membrane fiber recycling
[0383] GPC method for measuring Mn and Mw
[0384] The same sulfone GPC method #1 as described above was used.
[0385] Raw materials used for sample E15
[0386] Na2CO3 (sodium carbonate), available from Solvay
[0387] DHDPS (4,4'-dihydroxydiphenyl sulfone or bisphenol S), available from Sigma-Aldrich
[0388] Sulfolane, available from Chevron Phyllis Chemical Company
[0389] PES6: Hollow fiber dialyzer DORA B-13PF, from Bain Medical Equipment (Guangzhou) Co., Ltd., based on PES with Mw=66619, Mn=21277, PDI=3.13. Elemental analysis was performed using a VarioMICRO cube CHNS analyzer from Elementar. The PVP content in the PES-based membrane fiber was found to be about 5 wt.%.
[0390] Synthesis of sample E15 - PES manufacturing using PES-based hemodialysis membrane filters (100 wt.% recirculation)
[0391] Hemodialysis PES6 membrane fiber (Mw=66619Da) was used as a reactant for sample E15. The fiber (42g) was cut into small pieces and slowly added to a 250mL four-necked round-bottom flask containing 80ml of sulfolane. Then 4,4'-dichlorodiphenyl sulfone (DCDPS) (1.25g, 4.38mmol), 4,4'-dihydroxydiphenyl sulfone (DHDPS) (1.075g, 4.3mmol) were added to the reactor. The reaction medium was heated at 180°C with stirring at 50RPM in a continuous nitrogen stream. After the fiber and monomer were completely dissolved, the stirring speed was increased to 200RPM. Once the reaction temperature reached 220°C, sodium carbonate (2.32g, 21.9mmol) was added to the reaction medium. The reaction medium was heated at 227°C for about 4.5h. The molecular weight growth of the polymerization was monitored via GPC. First, the polymer was depolymerized from Mw-66619-Da to Mw-22865-Da, and then repolymerized to the desired molecular weight of 45500-Da.
[0392] The polymerization reaction was quenched by adding about 45 mL of sulfolane. Subsequently, MeCl was purged through the reaction medium to terminate the polymer chains for 30 minutes. The reaction mass was coagulated in 1.2 liters of deionized (Milli Q) water in a Waring blender. The polymer powder was extracted with cold and hot water in an extraction kettle until the residual solvent level dropped to less than about 0.3 wt. %. The polymer powder was dried at 120°C for 24 hours.
[0393] exist The Mw, Mn and PDI of the resulting PES polymer sample E15 after coagulation and drying are reported in and compared to the starting PES material: PES6 material that was added to the reaction medium to make sample E15.
[0394] Table 4
[0395]
[0396] **GPC (sulfone) method using dichloromethane as mobile phase
[0397] For sample E15, which has 100 wt.% PES6 recycle, there is a decrease in Mw (-30%) relative to the original PES6 polymer. There is also a very small increase in the PDI value of 1.6% relative to the recycled PES6 polymer.
[0398] Example 5: PSU Recycling and PSU / PVP Recycling
[0399] Test Method
[0400] GPC method for measuring Mn and Mw
[0401] The same sulfone GPC method #1 as described above was used.
[0402] Thermogravimetric analysis (TGA)
[0403] TGA experiments were performed using a TA Instrument TGA Q500. TGA measurements were obtained by heating the sample from 20°C to 800°C at a heating rate of 10°C / min under nitrogen.
[0404] DSC
[0405] DSC was used to determine the glass transition temperature (Tg) and melting point (Tm) (if present). DSC experiments were performed using the Q100 of TA Instruments. The DSC curve was recorded by heating, cooling, reheating and then recooling the sample at a heating and cooling rate of 20°C / min between 25°C and 320°C. All DSC measurements were taken under nitrogen purge. Unless otherwise noted, the Tg value (and Tm value, if any) reported was provided using the second heating curve.
[0406] Elemental analysis
[0407] The elemental composition of some polymer samples was determined using a 2400CHN elemental analyzer from Perkin Elmer. The polymer samples were burned based on the classical Pregl-Dumas method. The resulting combustion gases were completely reduced to CO2, H2O, N2 and SO2. The gases were then separated via frontier chromatography. When the gases were stripped, they were measured by a thermal conductivity detector to determine the quantitative amounts of carbon, hydrogen, nitrogen and sulfur.
[0408] pass H Quantification of PVP by NMR analysis
[0409] The samples were dissolved in deuterated 1,1,2,2-tetrachloroethane. All samples were run on a 400MHz NMR at Bruker with D1 set to 15 seconds and 64 scans. The data were processed using MestReNova software. The relevant peaks were integrated and the weight percentage (wt.%) of PVP in the sample was determined using the following equation:
[0410]
[0411] in
[0412] ∫PVP and will denote the sum of all hydrogen protons of PVP;
[0413] ∫PSU will represent the sum of all hydrogen protons with PVP between 7ppm and 9ppm;
[0414] #H PVP and #H PSU indicate the number of protons corresponding to PVP and PSU molecules;
[0415] Molecular weight of PVP = 111.1 g / mol; and
[0416] g PVP + g PSU = weight of sample.
[0417] Raw materials for sample CE16-E21
[0418] N-Methylpyrrolidone (NMP), available from Sigma-Aldrich
[0419] K2CO3 (potassium carbonate), available from Armand Products
[0420] Bisphenol A "BPA" (4,4'-dihydroxydiphenyl sulfone), available from Covestro
[0421] DCDPS (4,4'-dichlorodiphenyl sulfone), available from Solvay Specialty Polymers Chloromethane, available from Matheson Gas Company
[0422] Methanol, available from Sigma-Aldrich
[0423] PSU1: P-3500 pellets (lot number P060467C), manufactured by Solvay Specialty Polymers, USA, having Mw = 78213 g / mol; Mn = 21996 g / mol; PDI = 3.55 as measured via sulfone GPC method #1
[0424] DSC=190.14℃
[0425] TGA=505.5℃
[0426] PSU2: in pellet form P-3500 (Batch No. 1901009833), manufactured by Solvay Specialty Polymers, USA, with Mw = 77267 g / mol; Mn = 22542 g / mol; PDI = 3.42
[0427] DSC=190.72℃
[0428] TGA=501.2℃
[0429] PSU3: Fiber based on PSU-PVP based hemodialysis machine from D.Braun, Germany
[0430] Mw=82969g / mol, Mn=22907g / mol, PDI=3.6
[0431] DSC=186.7℃
[0432] TGA=516.1℃
[0433] PVP content: 3.89wt.%, by H NMR
[0434] C: 71.97%
[0435] H: 5.15%
[0436] N: 0.45%
[0437] PVP (polyvinylpyrrolidone), available from Alf Aesar, having Mw = 371165 g / mol, Mn = 139881 g / mol, PDI = 2.65, as determined by the following GPC method #3:
[0438] Viscotek GPC Max (autosampler, pump and degasser) with TDA302 triple detector array consisting of RALS (right angle light scattering), RI (refractive index) and viscosity detector was used. The sample was prepared to be about 2 mg / mL in DMAc / LiBr. The sample was run at 1.0 mL / min through a set of 3 columns at 65 ° C in NMP containing 0.2 w / w% LiBr: guard column (CLM1019-with 20k Da exclusion limit), high Mw column (CLM1013, 10 MM Daltons relative to polystyrene exclusion) and low Mw column (CLM1011-with 20k Daltons relative to PS exclusion limit). Calibration was completed using a single monodisperse polystyrene standard of about 100 k Da. Light scattering, RI and viscosity detectors were calibrated based on a set of input data provided according to the standard. The sample was prepared to be about 2 mg / mL in NMP / LiBr. Viscotek's OMNISec v4.6.1 software was used for data analysis.
[0439] PVP has a DSC value of 174.48°C (Tg) and a degradation onset temperature of 401°C (via TGA).
[0440] Synthesis of sample CE16 (counterexample): Baseline PSU production in NMP
[0441] Bisphenol A=BPA (182.63 g), DCDPS (229.72 g), K2CO3 (120.5 g) and NMP (532 g) were added to a 1-L 4-neck resin kettle equipped with an overhead stirrer, nitrogen inlet, thermocouple and Dean-Stark trap with condenser. The corresponding weights of the ingredients used in the reaction medium are provided in . The DCDPS / BPA molar ratio used in the reaction was 1.096, and the K2CO3 / BPA molar ratio was 1.09. The reactor was heated slowly, with a low agitator rpm used to mix the materials. The heating ramp rate was about 2.5-3°C / min until 190°C. When the temperature reached 190°C, condensed water was collected in the Dean-Stark trap. After the predetermined torque or polymerization time had been reached, the reaction was stopped by terminating the delivery of excess methyl chloride. The cooled reaction medium was then filtered to remove the KCl salts and then coagulated in methanol, and the coagulated polymer was washed with hot water (70°C) and methanol and then dried in a vacuum oven at 110°C for 12 hours.
[0442] This method produced a baseline PSU sample CE16 and Its Mw, Mn, PDI (using the GPC sulfone method), TGA data and Tg (via DSC) are provided in.
[0443] Synthesis of sample E17: PSU production with 25 wt.% PSU recycle in NMP
[0444] The synthesis was carried out using the same method as described for CE16 except that PSU P-3500 pellets (PSU1) were additionally charged into a 1-L 4-neck resin kettle to achieve a PSU recycle ratio of 25 wt.%. The corresponding weights of the ingredients are provided in . The DCDPS / BPA molar ratio used in the reaction was 1.096, and the K2CO3 / BPA molar ratio was 1.09. This produced PSU sample E17, and Its Mw, Mn, PDI (using the GPC sulfone method), TGA data and Tg (via DSC) are provided in.
[0445] Elemental analysis of sample E17: C = 72.43%, H = 4.88%, N < 0.05%
[0446] Synthesis of sample E18 : PSU production with 75% PSU recycle ratio in NMP
[0447] The synthesis was carried out using the same method as described for CE16 except that PSU P-3500 pellets (PSU1) were additionally charged into a 1-L 4-neck resin kettle to achieve a PSU recycle ratio of 75 wt.%. The corresponding weights of the ingredients are provided in . The DCDPS / BPA molar ratio used in the reaction was 1.096, and the K2CO3 / BPA molar ratio was 1.09. This produced PSU sample E18, and Its Mw, Mn, PDI (using sulfone GPC method), TGA data and Tg (via DSC) are provided in.
[0448] Elemental analysis of sample E18: C = 72.63%; H = 5.09%; N < 0.05%
[0449] Synthesis of sample E19: Production of PSU containing 5 wt.% PVP with 25 wt.% PSU recycle in NMP
[0450] The synthesis was carried out using the same method as described for CE16 except that PSU P-3500 pellets (PSU1) and PVP were additionally charged into a 1-L 4-neck resin kettle to achieve a PSU recycle ratio of 25 wt.%. The corresponding weights of the ingredients are provided in . The DCDPS / BPA molar ratio used in the reaction was 1.096, and the K2CO3 / BPA molar ratio was 1.09. This produced PSU sample E19, and Its Mw, Mn, PDI (using sulfone GPC method), TGA data and Tg (via DSC) are provided in.
[0451] Elemental analysis of sample E19 (C=72.4%, H=5.13%, N=0.09%) confirmed the presence of PVP in the resulting PSU sample E19. PVP was present in the final PSU sample E19 as PVP physically and chemically bound to the PSU polymer matrix.
[0452] Synthesis of sample E20: Production of PSU / PVP containing 5 wt. % PVP with 75 wt. % PSU recycle in NMP
[0453] The synthesis was carried out using the same method as described for CE16 except that PSU P-3500 pellets (PSU2) and PVP were additionally charged into a 1-L 4-neck resin kettle to achieve a PSU recycle ratio of 75 wt.%. The corresponding weights of the ingredients are provided in . The DCDPS / BPA molar ratio used in the reaction was 1.096, and the K2CO3 / BPA molar ratio was 1.09. This produced PSU sample E20, and Its Mw, Mn, PDI (using the GPC sulfone method), TGA data and Tg (via DSC) are provided in.
[0454] Elemental analysis of sample E20: C = 72.2%, H = 5.08%, N = 0.28% confirms the presence of PVP in the resulting PSU sample E20. PVP is present in the final PSU sample E20 as PVP is physically and chemically bound to the PSU polymer matrix.
[0455] Synthesis of sample E21: Production of PSU with 25% Braun dialyzer fibers in NMP
[0456] The synthesis was performed using the same method as described for CE16, except that fibers from the Braun dialyzer (PSU3) were additionally charged into the 1-L 4-neck resin kettle to achieve a PSU recycle ratio of 25 wt.%. The corresponding weights of the ingredients are provided in . The DCDPS / BPA molar ratio used in the reaction was 1.096, and the K2CO3 / BPA molar ratio was 1.09. This produced PSU sample E21, and Its Mw, Mn, PDI (using the GPC sulfone method), TGA data and Tg (via DSC) are provided in.
[0457] Table 5: Composition of reaction medium
[0458]
[0459] *This amount of PSU3 fiber contains about 3.89 wt.% PVP
[0460] Table 6
[0461]
[0462] **Sulfone GPC Method #1 using dichloromethane as mobile phase
[0463] Elemental analysis of sample E21: C = 72.53%, H = 5.31%, N = 0.11% confirmed the presence of PVP in the resulting PSU sample E21. PVP was present in the final PSU sample E21 as PVP physically and chemically bound to the PSU polymer matrix.
[0464] Example 6: PPSU Recycling
[0465] GPC Method for Measuring Mn, Mw (Sulfone GPC Method #2)
[0466] The following sulfone GPC method #2 was used for sample E22-25. Molecular weights were measured by gel permeation chromatography (GPC) using dichloromethane as the mobile phase. Separation was performed using two 5μ mixed D columns with guard columns from Agilent Technologies. Chromatograms were obtained using a UV detector at 254nm. A flow rate of 1.5ml / min of a 0.2w / v% solution in the mobile phase and an injection volume of 15μL were selected. Calibration was performed using a 10-point narrow molecular weight polystyrene standard. The injection volume of the calibration standard was 75μL. The number average molecular weight Mn and the weight average molecular weight Mw were reported, and PDI = Mw / Mn was calculated.
[0467] Raw materials used for samples E22-E25
[0468] Anhydrous sulfolane, available from Chevron Phyllis Chemical Company
[0469] DMI (1,3-dimethyl-2-imidazolidinone), available from TCI America
[0470] NMP (N-methylpyrrolidone), available from Sigma-Aldrich
[0471] Anhydrous K2CO3 (potassium carbonate) with an average particle size of 30-40 μm, available from Armand Products
[0472] Biphenol (4,4'-biphenol), available from Sigma-Aldrich
[0473] DCDPS (4,4'-dichlorodiphenyl sulfone), available from Solvay Specialty Polymers, USA
[0474] Methyl chloride, available from Matheson Gas Company
[0475] MCB (monochlorobenzene), available from Sigma-Aldrich
[0476] Methanol, available from Sigma-Aldrich
[0477] PPSU1: PPSU in solidified form, manufactured by Solvay Specialty Polymers, USA, with Mw = 60,925 g / mol, Mn = 28,501 g / mol, PDI = 2.14
[0478] PPSU2: Radel R-5600P NT PPSU in the form of ground powder, available from Solvay Specialty Polymers, USA, with Mw = 46,720 g / mol, Mn = 20,104 g / mol, PDI = 2.32.
[0479] PPSU3: PPSU in solidified form, manufactured by Solvay Specialty Polymers, USA, with Mw = 79,859 g / mol, Mn = 34,451 g / mol, PDI = 2.32
[0480] PPSU4: PPSU in solidified form, manufactured by Solvay Specialty Polymers, USA, with Mw = 69,652 g / mol, Mn = 31,259 g / mol, PDI = 2.23
[0481] PPSU5: PPSU in solidified form, manufactured by Solvay Specialty Polymers, USA, with Mw = 69,420 g / mol, Mn = 31,334 g / mol, PDI = 2.22
[0482] Synthesis of PPSU1
[0483] 130.34g (0.70mol) biphenol, 203.02g (0.707mol) DCDPS and 101.58g (0.735mol) anhydrous potassium carbonate are loaded into a 1-L 4-neck resin kettle equipped with an overhead stirrer, a nitrogen inlet and a Dean-Stark water trap with a condenser. 420.48g of DMI is added to the reactor. The reaction medium is stirred and heated to an internal temperature of 200°C via an external oil bath in about 90 minutes. The water of reaction is collected in the Dean-Stark water trap during heating. After reaching a predetermined torque, the reaction medium is bubbled through gaseous methyl chloride for 30min (about 1g / min). 323g of NMP is added to dilute the reaction medium. The reaction medium is pressure filtered to remove salts by a 2.7 μm glass fiber filter pad. The polymer solution is coagulated in methanol using a 1:5 polymer to methanol ratio using a Waring high-speed blender. The coagulated polymer is washed with methanol five times. The coagulated form was dried in a vacuum oven at 120°C for 12-20 hours and analyzed for Mw, Mn and PSI. The coagulated form was used in this example.
[0484] Synthesis method of PPSU4 and PPSU5
[0485] 83.80g (0.45mol) biphenol, 131.17g (0.4568mol) DCDPS and 71.52g (0.5175mol) anhydrous potassium carbonate are loaded into a 1-L 4-neck resin kettle equipped with an overhead stirrer, a nitrogen inlet and a Dean-Stark water separator with a condenser. The contents are evacuated / purged three times using vacuum / nitrogen circulation. 420.48g of sulfolane is added to the reactor. The reaction medium is stirred and heated to an internal temperature of 210°C in about 90 minutes via an external oil bath. The water of reaction is collected in the Dean-Stark water separator during heating. After reaching a predetermined torque, the reaction medium is bubbled through gaseous methyl chloride for 30min (about 1g / min). 723.6g of MCB and 61.92g of sulfolane are added to dilute the reaction medium. Pressure filtration is performed on the reaction medium by a 2.7 μm glass fiber filter pad to remove these salts. The polymer solution was coagulated in methanol using a Waring high speed blender using a 1:5 polymer to methanol ratio. The coagulated polymer was washed five times with methanol and then dried in a vacuum oven at 120°C for 12-20 hours.
[0486] Synthesis of PPSU3
[0487] A 60-gallon Hasteloy reactor vessel was charged with sulfolane followed by diphenol, potassium carbonate and DCDPS. A DCDPS / diphenol molar ratio of 1.015 and an excess of potassium carbonate of 11 mol.% relative to diphenol were used. Sulfolane was added to achieve a 30 wt.% polymer concentration. Polymerization was carried out at 210°C until the desired polymerization endpoint was achieved. MCB was added to quench the reaction followed by MeCl to terminate / end-cap the polymerization. The reaction mixture was diluted to 10% polymer concentration with MCB and sulfolane. A sample of approximately 1 liter of the reaction mixture was pressure filtered to remove salts and coagulated / dried as previously described.
[0488] General Synthesis of PPSU Samples E22-E25:
[0489] Biphenol, DCDPS, PPSU materials (as reactants), K2CO3 and sulfolane are loaded into a 1-L 4-neck resin kettle equipped with an overhead stirrer, a nitrogen inlet, a thermocouple and a Dean-Stark water separator with a condenser to achieve a DCDPS / biphenol molar ratio of 1 or 1.015 (for E23) and a K2CO3 / biphenol molar ratio of 1.15. The target polymer content in the reaction medium is 30wt.%. The reactor is then slowly heated (via an externally controlled oil bath) while stirring to mix the reaction medium. The reaction medium is heated to 210°C in approximately 90 minutes. After having reached a predetermined torque or polymerization time, gaseous MeCl is bubbled through the reaction medium with approximately 1g / min for end-capping 30min. A mixture of 859g of monochlorobenzene and 42g of sulfolane is added to the polymerization mixture. The cooled reaction medium was then pressure filtered to remove the formed KCl and unreacted K2CO3 salts and then coagulated in methanol using a Waring high speed blender using a 1:5 polymer to methanol ratio. The coagulated polymer was washed five times with methanol and then dried in a vacuum oven at 120°C for 12-20 hours.
[0490] exist The corresponding weights of the ingredients of PPSU samples E22-E25 are provided in.
[0491] Table 7: Composition of reaction medium
[0492]
[0493] exist The Mw, Mn and PDI (using GPC Sulfone Method #2) of the resulting PPSU samples E22-E25 are reported in.
[0494] Table 8
[0495]
[0496] **Sulfone GPC Method #2 using dichloromethane as mobile phase
[0497] Example 7: PSU manufacturing using 10 wt.% or 50 wt.% PSU recycling ratio
[0498] GPC method for measuring Mn and Mw
[0499] GPC Sulfone Method #1 was used in this example.
[0500] Raw materials for samples CE27-CE29 and E30-E32
[0501] DMSO (dimethyl sulfoxide), available from Fisher-Scientific
[0502] NaOH (sodium hydroxide), available from Fisher Scientific
[0503] Bisphenol A "BPA" (4,4'-dihydroxydiphenyl sulfone), available from Hexion
[0504] DCDPS (4,4'-dichlorodiphenyl sulfone), available from Solvay Specialty Polymers, USA
[0505] MeCl (methyl chloride), available from Matheson Gas Company
[0506] PSU7: in pellet form P-3500 PSU, available from Solvay Specialty Polymers, USA, has Mw=78385 g / mol, Mn=22755 g / mol, and PDI=3.44.
[0507] Strong base synthesis of samples CE27-CE29 and E30-E32
[0508] The blend of PSU pellets (reactants) and DMSO + MCB (319g) was loaded into a 1-L 4-neck resin kettle (reactor) equipped with an overhead stirrer, a nitrogen inlet, a thermocouple, a Barrett water trap, and a reflux condenser. A pressure equalizing funnel containing a caustic solution was attached to the top of the kettle. The reactor was purged with nitrogen until the PSU pellets were dissolved. For samples made with a 10wt.% PSU recycling ratio, the PSU pellets were dissolved at ambient temperature, and for samples made with a 50wt.% PSU recycling ratio, the PSU pellets were dissolved at 40°C. After dissolution, bisphenol A was added to the kettle, the reaction medium was purged for 15 minutes and then heated to reflux, during which caustic was added to the reaction medium. After reflux, the reaction medium was dehydrated by removing the water / MCB mixture. During dehydration, a solution of DCDPS in MCB (129g) was prepared in a heated pressure equalizing funnel. After removing all the water added and formed in the reaction, the DCDPS solution was added to the kettle.
[0509] After having reached the predetermined torque or polymerization time, the mixture was diluted with 400g MCB, while gaseous MeCl was bubbled through the reaction medium for 30min with about 1g / min for end-capping. After cooling, the reaction medium was further diluted with 400g MCB and pressure filtered to remove the NaCl salt formed. The polymer solution after filtration was then coagulated in methanol using a 1:5 polymer to methanol ratio using a Waring high-speed blender. The coagulated polymer was washed with methanol five times and then dried in a vacuum oven at 120°C for 12-20 hours.
[0510] exist The corresponding weights of the components of PSU samples CE27-CE29 and E30-E32 are provided in.
[0511] Table 10: Composition of reaction medium
[0512]
[0513] *DCDPS / BPA molar ratio, using MW DCDPS =287.16 g / mol; MW BPA =228.29 g / mol
[0514] **NaOH / BPA molar ratio, using MW BPA =228.29 g / mol; MW NaOH =39.997 g / mol
[0515] exist The Mw, Mn and PDI of the obtained PSU samples CE27-CE29 and E30-E32 are reported in.
[0516] Table 11
[0517]
[0518] **Sulfone GPC Method #1 using dichloromethane as mobile phase
[0519] Therefore, the scope of protection is not limited by the description listed above, but only by the following claims. Each claim is incorporated into this specification as an embodiment of the present invention. Therefore, the claims are a further description and an addition to the preferred embodiments of the present invention.
Claims
1. A method for producing polyarylethersulfone (P2) using a recycled polymer material containing polyarylethersulfone (P1) as a reactant, the method comprising Adding a polar aprotic solvent (S) to the reactor vessel; adding recycled polymer material containing polyarylethersulfone (P1) to the reactor vessel; Adding a basic salt-forming agent (A) to the reactor vessel; adding at least one monomer (M) selected from the group consisting of at least one aromatic diol monomer (AA) and at least one aromatic dihalogenated monomer (BB) to the reactor vessel; whereby said adding step forms a reaction medium (RM) comprising: the recycled polymer material containing the polyarylethersulfone (P1), the at least one monomer (M), the basic salt-forming agent (A) and the polar aprotic solvent (S), heating the reaction medium to reach a reaction temperature of at least 150° C. to form polyarylethersulfone (P2); and separating the polyarylethersulfone (P2) formed from the reaction medium; The alkaline salt-forming agent (A) is an alkali metal carbonate and / or an alkali metal hydroxide.
2. The method of claim 1, wherein: - the aromatic diol monomers (AA) are selected from the group consisting of: 4,4'-biphenol, bisphenol A, bisphenol S, isosorbide, isomannide, isoidol, tetramethylbisphenol F, hydroquinone, and any combination thereof, preferably selected from the group consisting of: 4,4'-biphenol, bisphenol A, bisphenol S, tetramethylbisphenol F, hydroquinone, and any combination thereof, and / or - the aromatic dihalogenated monomer (BB) is selected from the group consisting of: 4,4'-difluorodiphenyl sulfone (DFDPS), 4,4'-dichlorodiphenyl sulfone (DCDPS), disulfonated DCDPS, disulfonated DFDPS, and any combination thereof, preferably selected from the group consisting of: DCDPS, disulfonated DCDPS, and combinations thereof; and / or The polar aprotic solvent (S) is selected from the group consisting of: 1,3-dimethyl-2-imidazolidinone (DMI), dimethyl sulfoxide (DMSO), dimethyl sulfone (DMSO2), diphenyl sulfone, diethyl sulfoxide, diethyl sulfone, diisopropyl sulfone, tetrahydrothiophene-1,1-dioxide (commonly known as tetramethylene sulfone or sulfolane), N-alkyl-2-pyrrolidones such as N-methyl -2-pyrrolidone (NMP), N-butylpyrrolidone (NBP), N-ethylpyrrolidone (NEP), N,N′-dimethylacetamide (DMAc), N,N′-dimethylpropyleneurea (DMPU), dimethylformamide (DMF), tetrahydrothiophene-1-monoxide, and any combination thereof.
3. The method according to claim 1 or 2, wherein: The polyarylethersulfone (P1) is derived from at least one aromatic diol monomer (AA') and at least one aromatic dihalogenated monomer (BB') by condensation, and wherein: - the added aromatic diol monomer (AA) is the same as or different from the aromatic diol monomer (AA'); and / or The additional aromatic dihalogenated monomers (BB) are identical to or different from the aromatic dihalogenated monomer (BB′).
4. The method according to any one of claims 1 to 3, wherein: The polyarylethersulfone (P1) comprises at least 50 wt.%, at least 60 wt.%, at least 70 wt.%, at least 80 wt.%, at least 90 wt.%, or at least 95 wt.% of a sulfone polymer selected from the group consisting of: -PPSU, -PSU, -PES, - Sulfonated PSU (sPSU), - Sulfonated PES (sPES), -sulfonated PPSU (sPPSU), - any polymer derived from a diol monomer selected from isosorbide and / or tetramethylbisphenol F and a dihalogenated monomer selected from sulfonated dihalodiphenyl sulfone and / or dihalodiphenyl sulfone, - any copolymer derived from at least two diols selected from diphenol, bisphenol A, bisphenol S, isosorbide, tetramethylbisphenol F and / or hydroquinone and a dihalogenated monomer selected from sulfonated dihalodiphenyl sulfones and / or dihalodiphenyl sulfones, - a block polymer of AB or ABA form comprising at least one block having one repeating unit selected from those of formula (L), (L'), (N), (N'), (O), (O'), (Q), (Q'), and at least one block having one repeating unit selected from those of formula (T), (T'), (U), (U'), (V), (V'), (W), (W'), (U*), (V*), (W*); - a block copolymer of AB or ABA form comprising at least one block having one repeating unit selected from those having formula (L), (L'), (N), (N'), (O), (O'), (Q), (Q'), and at least one polyalkylene oxide or polyvinylpyrrolidone (PVP) block, such as a PEG block, a PPG block or a PVP block; and - any combination of two or more thereof, Wherein these formulas (L), (L'), (N), (N'), (O), (O'), (Q), (Q'), (T), (T'), (U), (U'), (V), (V'), (W), (W'), (U*), (V*), (W*) are as follows: in: - each R is independently selected from the group consisting of halogen, alkyl, alkenyl, alkynyl, aryl, ether, thioether, carboxylic acid, ester, amide, imide, alkali metal or alkaline earth metal sulfonate, alkyl sulfonate, alkali metal or alkaline earth metal phosphonate, alkyl phosphonate, amine and quaternary ammonium; and - Each i is independently an integer from 1 to 4.
5. The method according to any one of claims 1 to 4, wherein: The polyarylethersulfone (P1) is selected from the group consisting of -PPSU, -PSU, -PES, - Sulfonated PSU, -Sulfonated PES, -Sulfonated PPSU, - any polymer derived from a diol monomer selected from isosorbide and / or tetramethylbisphenol F and a dihalogenated monomer selected from sulfonated dihalodiphenyl sulfone and / or dihalodiphenyl sulfone, - any copolymer derived from at least two diols selected from diphenol, bisphenol A, bisphenol S, isosorbide, tetramethylbisphenol F and / or hydroquinone and a dihalogenated monomer selected from sulfonated dihalodiphenyl sulfones and / or dihalodiphenyl sulfones, - a block polymer in the form of AB or ABA, comprising at least one sulfone polymer block having one repeating unit selected from those of PPSU, sPPSU, PSU, sPSU, PES, sPES, and at least one block having one repeating unit made from tetramethylbisphenol F and sulfonated or non-sulfonated dihalodiphenyl sulfone or from 1,4:3,6-dianhydrohexitol sugar diol and sulfonated or non-sulfonated dihalodiphenyl sulfone; - a block copolymer in the AB or ABA form comprising at least one block polymer having one repeating unit selected from those of PPSU, sPPSU, PSU, sPSU, PES, sPES, and at least one polyalkylene oxide or polyvinylpyrrolidone (PVP) block, such as a PEG block, a PPG block or a PVP block; and - Any combination of two or more thereof.
6. The method according to any one of claims 1 to 5, wherein: The recycled polymer material further comprises another polymer (P3) different from the polyarylethersulfone (P1), preferably a pore-forming polymer such as polyvinylpyrrolidone (PVP), a polyalkylene oxide such as PEG, or a combination thereof; and wherein the recycled polymer material comprises - a blend of the polyarylethersulfone (P1) and the other polymer (P3) and / or - a block copolymer comprising at least one block of the polyarylethersulfone (P1) and at least one block of the further polymer (P3).
7. The method according to any one of claims 1 to 6, wherein: The recycled polymeric material further comprises non-polymeric fillers, such as particulate mineral fillers, carbon fibers and / or glass fibers.
8. The method according to any one of claims 1 to 7, wherein: The recycled polymeric material comprises at least one material selected from the group consisting of: post-consumer polymer articles, post-industrial polymer articles including article waste, off-specification polyarylethersulfone products; and any combination thereof, wherein the article is preferably selected from the group consisting of: films, automotive parts, electronic parts, consumer product parts such as baby bottles, composite materials, battery parts, and any combination thereof.
9. The method according to any one of claims 1 to 8, wherein: - the added polyarylethersulfone (P1) is PES, the formed polyarylethersulfone (P2) is a PES homopolymer or copolymer, and the at least one monomer (M) added to the reactor vessel is bisphenol S; or - the added polyarylethersulfone (P1) is PSU, the formed polyarylethersulfone (P2) is a PSU homopolymer or copolymer, and the at least one monomer (M) added to the reactor vessel is bisphenol A; or The added polyarylethersulfone (P1) is PPSU, the formed polyarylethersulfone (P2) is a PPSU homopolymer or copolymer, and the at least one monomer (M) added to the reactor vessel is 4,4′-biphenol.
10. The method according to any one of claims 1 to 9, wherein: The polyarylethersulfone (P2) has an Mw of (P1) Mw within + / -35% (P2) , where the Mw (P1) and the Mw (P2) is measured via a GPC method using dichloromethane as the mobile phase and calibrated with polystyrene standards; and / or The polyarylethersulfone (P2) has a PDI of P1 PDI within + / -35% of value P2 The PDI value is denoted as PDI wherein PDI is the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn), each of Mw and Mn being measured via a GPC method using dichloromethane as the mobile phase and calibrated with polystyrene standards.
11. The method according to any one of claims 1 to 10, wherein: The polyarylethersulfone (P2) has an Mw of at least 40 kDa, preferably at least 50 kDa, more preferably from 50 kDa to 100 kDa or from 55 kDa to 90 kDa. (P2) , the Mw (P2) It was measured via a GPC method using dichloromethane as the mobile phase and calibrated with polystyrene standards.
12. The method according to any one of claims 1 to 11, wherein: The recycled polymer material comprising the polyarylethersulfone (P1) is added to the reactor vessel in solid form, such as pellets, fibers, flakes, powders, chopped or ground articles, solidified particles, or any other solid 3-D object, or in the form of a solution or slurry, wherein at least a portion of the polyarylethersulfone (P1) is dissolved prior to addition to the reactor vessel.
13. The method according to any one of claims 1 to 12, wherein: The separation step comprises solidification of the polyarylethersulfone (P2), and / or The method further comprises at least one of the following steps between the reacting step and the separating step: - cooling the reaction medium; - adding a solvent (S) which is the same as or different from the polar aprotic solvent (S) q ) to quench the reaction medium; and / or - Adding a capping agent to convert the hydrocarbyl end groups of the formed polyarylethersulfone (P2) into less reactive end groups.
14. The process of any one of claims 1 to 13, which is carried out at a recycle ratio of polyarylethersulfone (P1) in the reaction medium of 100 wt.% to 1 wt.%, the recycle ratio being calculated as the ratio of the weight of the added polyarylethersulfone (P1) based on the combined weight of the added polyarylethersulfone (P1) and the maximum weight of the PAES polymer that would theoretically result from the polycondensation of the monomers (AA) and (BB) based on equimolar stoichiometry when both the diol monomer (AA) and the dihalogenated monomer (BB) are added to the reaction medium.
15. The method according to any one of claims 1 to 14, wherein: The at least one monomer (M) comprises at least one aromatic diol monomer (AA), and in - the condensation reaction is carried out in a molar ratio of the alkaline salt-forming agent to the diol monomer (AA) of at least 1 and at most 2, and / or - The diol (AA) and the basic salt-forming agent (A) are added to the reactor vessel in the form of the basic salt (AAA) of the diol (AA).
16. The method according to any one of claims 1 to 15, wherein: The reaction temperature is - at least 160°C, at least 165°C, at least 170°C, at least 175°C, at least 180°C, at least 185°C, at least 190°C, at least 195°C, or at least 200°C; and / or - up to 350°C, up to 300°C, up to 295°C, up to 290°C, up to 285°C, up to 280°C, up to 275°C, up to 270°C, up to 265°C, or up to 260°C.
17. Polyarylethersulfone (P2) obtainable by the process according to any one of claims 1 to 16.
18. An article comprising the polyarylethersulfone (P2) according to claim 17, the article being preferably selected from the group consisting of a membrane, a fiber, a sheet, a solution-processed film, a solution-processed monofilament, and any combination thereof.
Citation Information
Patent Citations
Process for preparing branched polyarylene ethers
US20050154178A1
Poly(ether sulfone)s and poly(ether amide sulfone)s and methods of their preparation
US20160002431A1
Polyarylene polyethers
US4108837A
Polyarylene polyethers
US4175175A
Cited By
Permanent hydrophilic block structure polyarylether sulfone hemodialysis membrane and preparation method thereof
CN120285804A
The use of at least one recycled polyarylene ether sulfone polymer in a method for the preparation of a membrane
WO2026175986A1